Method for recovering target metal from iron or steel slag using at least one of carbothermic reduction process and pyro-hydrometallurgical process

JP2025028919AActive Publication Date: 2025-03-05THE GOVERNING COUNCIL OF THE UNIV OF TORONTO +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024203319
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-27
Filing Date
2024-11-21
Publication Date
2025-03-05
Estimated Expiration
2040-03-27

Smart Images

  • Figure 2025028919000001_ABST
    Figure 2025028919000001_ABST
Patent Text Reader

Abstract

To provide pyro-hydrometallurgical methods to economically and environmentally recover a target metal from iron slag or steel slag.SOLUTION: For instance, the method enables subjecting an iron or steel slag feed to acid-baking with an acid to produce a dried mixture comprising at least one soluble metal salts, then subjecting the dried mixture to water leaching to make an aqueous solution comprising an aqueous leachate rich in the target metal and solid residues and subsequently separating the aqueous leachate rich in the target metal from the solid residues. This acid-baking water-leaching method facilitates efficient recovery of target metal compared to conventional methods.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority under applicable law to U.S. Provisional Application No. 62 / 824.588, filed March 27, 2019, the contents of which are incorporated herein by reference in their entirety for all purposes.

[0002] The technical field relates generally to methods for recovering at least one valuable element from metallurgical slags, such as iron and steel slags, and more specifically to methods for recovering at least one desired metal from iron and steel slags utilizing at least one of a carbothermal reduction process and a high-temperature hydrometallurgical process. [Background technology]

[0003] As the importance of valorization of waste is increasingly emphasized to establish a circular economy, technosphere mining (i.e., extraction of strategic materials from alternative secondary resources such as industrial waste residues) is in the spotlight. For example, the alternative secondary resource can be metallurgical slags, such as ferrous slags, including iron slags and steel slags, generated by the iron and steel manufacturing or steel smelting industries during the separation of molten iron or steel from its impurities in the iron or steel furnaces.

[0004] Approximately 15-20 million tons of steel slag are produced annually in the United States alone. Disposal of steel slag poses environmental hazards. In fact, approximately 15%-40% of steel slag is stored at steel plants and then sent to landfills.

[0005] Iron and steel slags contain significant amounts of valuables such as titanium, niobium, platinum group metals (abbreviated as PGMs), gold, silver, and rare earth elements (abbreviated as REEs). For example, electric arc furnace (EAF) slag is a significant potential source of many valuable metals including, but not limited to, iron, manganese, magnesium, chromium, niobium, and aluminum.

[0006] These values ​​can be recovered and added valued through extractive metallurgy. As a result, the extraction of values ​​helps conserve natural resources and saves landfill space. It also means increased profits for the steel manufacturing industry in an environmentally sustainable way.

[0007] Traditionally, extraction of Nb, Ti, and REEs from primary and secondary sources is carried out by hydrometallurgical methods such as direct acid leaching (Valighazvini et al., Industrial & Engineering Chemistry Research 52, no. 4 (2013): 1723-1730; El-Hussaini et al., Hydrometallurgy 64, no. 3 (2002): 219-229; and Kim et al., Minerals 6, no. 3 (2016): 63).

[0008] However, several challenges may be faced when using traditional hydrometallurgy. For example, traditional hydrometallurgy requires several pretreatment steps. Major concerns associated with traditional hydrometallurgy include the consumption of large amounts of acids, bases, and organic solvents, as well as the production of large amounts of hazardous waste. In another example, Zheng et al. prepared titanium dioxide from Ti-loaded electric furnace slag by using NH4HF2-HF leaching and hydrolysis processes (Zheng et al., Journal of hazardous materials 344 (2018): 490-498). However, the use of hydrofluoric acid-based leaching agents has significant adverse effects on the environment.

[0009] Processes based on combined high-temperature hydrometallurgy, such as the acid calcination-leaching process, are an alternative to direct leaching. Using high-temperature hydrometallurgy, the metal-bearing sample is mixed with concentrated acid, calcined in a furnace at elevated temperature, and then leached at ambient temperature. This process provides increased extraction efficiency with shorter residence times, smaller leachate volumes, and significantly reduced acid consumption compared to traditional hydrometallurgy.

[0010] There are only a few reports on the extraction of valuable materials by high-temperature hydrometallurgical processes. For example, Wu et al. proposed roasting Ta-Nb ores with concentrated sulfuric acid and leaching the calcined samples with dilute sulfuric acid (Wu et al., In Advanced Materials Research, vol. 997, pp. 651-654. Trans Tech Publications Ltd, 2014). Although Wu et al. obtained high leaching efficiency, there are some drawbacks associated with acid leaching and high leaching temperature. In another example, Qu et al. proposed extracting titanium from titanium-bearing electric arc furnace slag by acid calcination and leaching with water at elevated temperatures of 50°C to 80°C (Qu et al., Journal of Materials Science Research Vol. 5, No. 4 (2016)). Qu et al. achieved only a moderate leaching efficiency of 84.3% and used high leaching temperatures. Achieved.

[0011] Carbothermal reduction processes are also used to reduce metal oxides, thereby producing metals. For example, using this type of process, iron oxides are reduced with carbonaceous materials such as coal, coke, and natural gas to extract metals.

[0012] Therefore, there is a need for a process that overcomes one or more of the shortcomings encountered in conventional iron and steel slag technosphere mining processes. Summary of the Invention

[0013] According to a first aspect, the present technology relates to a method for recovering a target metal from an iron or steel slag, the method comprising: mixing the iron or steel slag particles and the acid together in a ratio of acid to iron or steel slag particles by weight ranging from about 0.5 to about 5 to form a mixture; calcining the mixture at a temperature between about 100° C. and about 600° C. to digest the mixture and remove excess water and acid to produce a dry mixture comprising pyrolysis gases and at least one soluble metal salt; leaching the dry mixture by adding water to obtain a density in the range of about 50 g / L to about 250 g / L to produce an aqueous solution containing said target metal-rich aqueous leachate and a solid residue; separating said target metal-rich aqueous leachate from said solid residue; Includes.

[0014] In one embodiment, the target metal is at least one of titanium, niobium, manganese, chromium, iron, scandium, neodymium, yttrium, lanthanum, cerium, samarium, gadolinium, dysprosium, praseodymium, europium, terbium, erbium, calcium, magnesium, aluminum, copper, silicon, ruthenium, rhodium, palladium, osmium, iridium, and platinum.

[0015] In another embodiment, the method further comprises grinding the iron or steel slag particles prior to mixing. In one example, the grinding is performed by ball milling.

[0016] In another embodiment, the method further comprises classifying and separating the iron or steel slag particles into fractions by size. In one example, the iron or steel slag particles have a size of less than about 200 mesh. In another example, the iron or steel slag particles have a diameter ranging from about 1 μm to about 150 μm, or from about 1 μm to about 140 μm, or from about 1 μm to about 130 μm, or from about 1 μm to about 120 μm, or from about 1 μm to about 110 μm, or from about 1 μm to about 100 μm, or from about 1 μm to about 90 μm, or from about 5 μm to about 90 μm.

[0017] In another embodiment, the method further includes drying the iron or steel slag particles prior to mixing. In one example, the drying is performed at a temperature ranging from about 50° C. to about 80° C. In another example, the drying is performed for a period ranging from about 12 hours to about 24 hours.

[0018] In another embodiment, the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and a mixture of at least two thereof. In one example, the acid comprises sulfuric acid and the soluble metal salt comprises at least one soluble metal sulfate salt.

[0019] In another embodiment, the acid to iron or steel slag particle mass ratio ranges from about 1 to about 3, or from about 2 to about 3, or from about 1 to about 1.75.

[0020] In another embodiment, the calcination is carried out at a temperature of about 100°C to about 500°C, or about 200°C to about 600°C, or about 200°C to about 500°C, or about 200°C to about 400°C, or about 300°C to about 400°C.

[0021] In another embodiment, the baking is carried out for a period ranging from about 30 minutes to about 240 minutes, or from about 30 minutes to about 120 minutes, or from about 30 minutes to about 60 minutes.

[0022] In another embodiment, the method further comprises recycling the pyrolysis gas. In one example, recycling the pyrolysis gas comprises reusing the pyrolysis gas in the mixing step.

[0023] In another embodiment, the leaching step is carried out for a period ranging from about 30 minutes to about 360 minutes, or from about 120 minutes to about 360 minutes, or from about 180 minutes to about 360 minutes.

[0024] In another embodiment, the density of the dry mix ranges from about 100 g / L to about 200 g / L, or from about 125 g / L to about 200 g / L, or from about 150 g / L to about 200 g / L.

[0025] In another embodiment, the method further comprises stirring the aqueous solution comprising the target metal-enriched aqueous leachate and the solid residue. In one example, the stirring is performed at a stirring speed of about 150 rpm to about 650 rpm.

[0026] In another embodiment, the separation comprises filtering the aqueous solution comprising the aqueous leachate rich in said target metal and a solid residue.

[0027] In another embodiment, the method further comprises purifying said target metal-enriched aqueous leachate. In one example, the purification step is performed by at least one of selective precipitation, solvent extraction, and ion exchange.

[0028] According to another aspect, the present technology relates to a method for recovering niobium from iron or steel slag, the method comprising: mixing the iron or steel slag particles and the acid together to form a mixture in a ratio of acid to iron or steel slag particles by weight ranging from about 2.5 to about 3.5; calcining the mixture at a temperature between about 375° C. and about 425° C. to digest the mixture and remove excess water and acid to produce a dry mixture comprising pyrolysis gases and at least one soluble niobium salt; leaching the dry mixture by adding water to obtain a density in the range of about 175 g / L to about 225 g / L to produce an aqueous solution comprising a niobium-rich aqueous leachate and a solid residue; leaching the dry mixture by adding water to obtain a density in the range of about 50 g / L to about 70 g / L to produce an aqueous solution containing a scandium-rich leachate and a solid residue; and separating the niobium-rich aqueous leachate from the solid residue.

[0029] In one embodiment, the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and a mixture of at least two thereof. In one example, the acid comprises sulfuric acid and the soluble niobium salt comprises at least one soluble niobium sulfate salt.

[0030] In another embodiment, the acid to iron or steel slag particle mass ratio is about 3.

[0031] In another embodiment, the calcination is carried out at a temperature of about 400°C.

[0032] In another embodiment, the density of the dry mix is ​​about 200 g / L.

[0033] In another embodiment, the baking is carried out for a period ranging from about 30 minutes to about 240 minutes. In one example, the baking is carried out for a period of about 120 minutes.

[0034] In another embodiment, the method further comprises stirring the aqueous solution comprising the niobium-rich aqueous leach solution and the solid residue at a stirring speed of about 150 to about 600 rpm. In one example, the stirring speed is about 150 rpm.

[0035] According to another aspect, the present technology relates to a method for recovering titanium from iron or steel slag, the method comprising: mixing the iron or steel slag particles and the acid together in a mass ratio of acid to iron or steel slag particles ranging from about 2 to about 3 to form a mixture; calcining the mixture at a temperature between about 200° C. and about 400° C. to digest the mixture and remove excess water and acid to produce a dry mixture comprising pyrolysis gases and at least one soluble titanium salt; leaching the dry mixture by adding water to obtain a density in the range of about 50 g / L to about 200 g / L to produce an aqueous solution containing a titanium-rich aqueous leachate and a solid residue; separating the titanium-rich aqueous leachate from the solid residue; Includes.

[0036] In one embodiment, the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and a mixture of at least two thereof. In one example, the acid includes sulfuric acid and the soluble titanium salt includes at least one soluble titanium sulfate salt.

[0037] In another embodiment, the baking is carried out for a period ranging from about 30 minutes to about 120 minutes, or from about 30 minutes to about 90 minutes.

[0038] In another embodiment, the density of the dry mix ranges from about 60 g / L to about 200 g / L.

[0039] In another embodiment, the method further comprises stirring the aqueous solution comprising the titanium-rich aqueous leachate and the solid residue at a stirring speed ranging from about 150 rpm to about 550 rpm. In one example, the stirring speed ranges from about 200 rpm to about 550 rpm.

[0040] In another embodiment, the steel slag is electric arc furnace slag, the acid to steel slag particle mass ratio is about 3, the calcination is performed at a temperature of about 400° C., and the density of the dry mixture is about 200 g / L. In one example, the calcination is performed for a period of about 120 minutes. In another example, the method further includes stirring the aqueous solution comprising the titanium-rich aqueous leachate and the solid residue at a stirring speed of about 150 rpm.

[0041] In another embodiment, the iron slag is a blast furnace slag, the acid to iron slag particle mass ratio is about 2, the calcination is performed at a temperature of about 200° C., and the density of the dry mixture is about 62 g / L. In one example, the calcination is performed for a period of about 90 minutes. In another example, the method further includes stirring the aqueous solution containing the titanium-rich aqueous leachate and the solid residue at a stirring speed of about 600 rpm.

[0042] According to another aspect, the present technology relates to a method for recovering scandium from iron or steel slag, the method comprising: mixing the iron or steel slag particles and the acid together in a ratio of acid to iron or steel slag particles by weight ranging from about 1.5 to about 2.5 to form a mixture; calcining the mixture at a temperature between about 175° C. and about 225° C. to digest the mixture and remove excess water and acid to produce a dry mixture comprising pyrolysis gases and at least one soluble scandium salt; leaching the dry mixture by adding water to obtain a density in the range of about 50 g / L to about 70 g / L to produce an aqueous solution containing a scandium-rich aqueous leachate and a solid residue; separating the scandium-rich aqueous leachate from the solid residue; Includes.

[0043] In one embodiment, the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and a mixture of at least two thereof. In one example, the acid includes sulfuric acid and the soluble scandium salt includes at least one soluble scandium sulfate salt.

[0044] In another embodiment, the acid to iron or steel slag particle mass ratio is about 2.

[0045] In another embodiment, the calcination is carried out at a temperature of about 200°C.

[0046] In another embodiment, the density of the dry mix is ​​about 60 g / L.

[0047] In another embodiment, the baking is carried out for a period of time ranging from about 60 minutes to about 120 minutes. In one example, the baking is carried out for a period of time of about 90 minutes.

[0048] In another embodiment, the method further comprises stirring the aqueous solution comprising the scandium-rich aqueous leach solution and the solid residue at a stirring speed of about 600 rpm.

[0049] According to another aspect, the present technology relates to a method for recovering neodymium from iron or steel slag, the method comprising: mixing the iron or steel slag particles and the acid together in a ratio of acid to iron or steel slag particles by weight ranging from about 1.5 to about 2.5 to form a mixture; calcining the mixture at a temperature of about 175° C. to about 225° C. to digest the mixture and remove excess water and acid to produce a dry mixture comprising pyrolysis gases and at least one soluble neodymium salt; leaching the dry mixture by adding water to obtain a density in the range of about 50 g / L to about 70 g / L to produce an aqueous solution containing a neodymium-rich aqueous leachate and a solid residue; separating the neodymium-rich aqueous leachate from the solid residue; Includes.

[0050] In one embodiment, the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and a mixture of at least two thereof. In one example, the acid comprises sulfuric acid and the soluble neodymium salt comprises at least one soluble neodymium sulfate salt.

[0051] In another embodiment, the acid to iron or steel slag particle mass ratio is about 2.

[0052] In another embodiment, the calcination is carried out at a temperature of about 200°C.

[0053] In another embodiment, the density of the dry mix is ​​about 60 g / L.

[0054] In another embodiment, the baking is carried out for a period of time ranging from about 30 minutes to about 60 minutes. In one example, the baking is carried out for a period of time of about 30 minutes.

[0055] In another embodiment, the method further comprises stirring the aqueous solution comprising the neodymium-rich aqueous leach solution and the solid residue at a stirring speed of about 600 rpm.

[0056] According to another aspect, the present technology relates to a method for recovering target metals from iron or steel slag, the method comprising: mixing iron or steel slag particles, at least one reducing agent in a reducing agent to iron or steel slag particle mass ratio in the range of about 0.06 to about 0.12, and at least one flux in a flux to iron or steel slag particle mass ratio in the range of 0 to about 0.1 to form a mixture; smelting the mixture at a temperature of about 1300° C. to about 1800° C. to form a metal phase and a slag layer containing the target element; Separating a metal phase containing the target element from the slag phase to produce a metal phase containing the target element and a slag layer. Includes.

[0057] In one embodiment, the target metal is at least one of iron, manganese, chromium, and niobium. In one example, the target metal is iron.

[0058] In another embodiment, the iron or steel slag is electric arc furnace slag.

[0059] In another embodiment, the reducing agent comprises a carbon source. In one example, the carbon source is selected from the group consisting of metallurgical coal, charcoal, petroleum coke, pet coke, natural gas, and combinations of at least two thereof. In one important example, the carbon source is lignite.

[0060] In another embodiment, the reducing agent to iron or steel slag particle mass ratio is about 0.06, about 0.09, or about 0.12.

[0061] In another embodiment, the flux is selected from the group consisting of silica, alumina, and mixtures thereof. In one important example, the flux is alumina. In another important example, the flux is silica. In another important example, the flux is a mixture of silica and alumina.

[0062] In another embodiment, the reducing agent to iron or steel slag particle mass ratio is about 0.05, or about 0.1.

[0063] In another embodiment, the method further comprises crushing the iron or steel slag particles prior to mixing. In one example, the crushing is performed using at least one of a jaw crusher and a disk mill.

[0064] In another embodiment, the method further comprises classifying and separating the iron or steel slag particles into fractions by size.

[0065] In another embodiment, the iron or steel slag particles have a size of less than about 200 mesh.

[0066] In another embodiment, the method further includes drying the iron or steel slag particles prior to mixing. In one example, the drying is performed at a temperature of at least about 50° C. In another example, the drying is performed at a temperature ranging from about 50° C. to about 80° C. In another example, the drying is performed for a period of at least about 24 hours.

[0067] In another embodiment, the method further comprises pelletizing the mixture prior to the smelting step.

[0068] In another embodiment, the separation step is performed by a mechanical separation method, hi one example, the separation step is performed manually.

[0069] In another embodiment, the method further comprises grinding the slag phase to obtain slag particles.

[0070] In another embodiment, the method further comprises classifying and separating the slag particles into fractions by size.

[0071] In another embodiment, the method further includes reducing the target metal content in the slag phase to produce a target metal-depleted slag. In one example, reducing the target metal content in the slag phase is performed by magnetic separation. For example, the magnetic separation is performed using a Davis™ tube.

[0072] In another embodiment, the smelting step is carried out at a temperature in the range of about 1300° C. to about 1700° C., or about 1300° C. to about 1600° C., or about 1400° C. to about 1800° C., or about 1400° C. to about 1700° C., or about 1400° C. to about 1600° C., or about 1500° C. to about 1800° C., or about 1500° C. to about 1700° C., or about 1500° C. to about 1600° C. In one example, the smelting step is carried out at a temperature in the range of about 1500° C. to about 1600° C.

[0073] In another embodiment, the iron or steel slag is a by-product of an iron or steel making process. In one example, the iron or steel making process provides heat energy to the iron or steel slag. For example, the iron or steel slag particles are at an elevated temperature prior to the mixing step.

[0074] In another embodiment, the iron or steel slag particles and the reducing agent undergo an oxidation-reduction (redox) reaction that releases chemical energy, for example, a redox reaction that produces heat as a by-product (an exothermic reaction), or alternatively, the iron or steel slag particles and the reducing agent undergo an oxidation-reduction (redox) reaction that does not release chemical energy.

[0075] In another embodiment, the method further comprises subjecting the target metal-depleted slag to a high temperature hydrometallurgical process to recover a second target metal. In one example, the high temperature hydrometallurgical process is a method as described herein. [Brief description of the drawings]

[0076] [Figure 1] FIG. 1 is a flow diagram of a process for recovering valuable elements from iron and steel slags according to one embodiment. [Diagram 2] FIG. 1 is a schematic diagram of a process for recovering valuable elements from iron and steel slags according to one embodiment. [Diagram 3] FIG. 2 is a flow diagram of a process for recovering valuable elements from iron and steel slags according to another embodiment. [Figure 4] FIG. 2 is a graph of particle size distribution of pulverized electric arc furnace (EAF) slag as described in Example 1(a). [Diagram 5] FIG. 1 shows the characterization results of the ground EAF slag as described in Example 1(a), with (a) and (b) graphs of inductively coupled plasma optical emission spectroscopy (ICP-OES) results showing elemental composition, (c) an X-ray diffraction pattern, (d) a scanning electron microscope (SEM) image of the slag particles (scale bar represents 5 μm), and (d) energy dispersive X-ray spectroscopy (EDS) elemental mapping of the slag particles. [Figure 6] FIG. 1 shows the results of extraction efficiency of several elements at different factor levels as described in Example 1(d), with graphs of calcination temperature (a), acid to slag mass ratio (b), calcination time (c), slag to water density (d), and stirring speed (e). [Figure 7] Graphs of rate test results for various elements at calcination temperatures of 200° C. and 400° C., respectively, as described in Example 1(d) are shown in (a) and (b), and a graph of extraction efficiency for various elements at different acid to slag mass ratios is shown in (c), including additional test results at ratios of 1.25, 1.50, and 1.75. [Figure 8] 1 is a graph of the factor effect coefficients of the empirical extraction model as described in Example 1(e) showing (a) Nd results, (b) Ti results, (c) Fe results, (d) Ca results, (e) Mn results, (f) Mg results, (g) Al results, and (h) Cr results. The inset graph shows the correlation between the results predicted from the empirical model and the experimental results. [Figure 9] FIG. 1 shows the characterization results of EAF slag before and after the acid calcination process, as described in Example 1(g). (a) shows the XRD (X-ray powder diffraction) diffractograms of EAF slag before and after the acid calcination process, and (b)-(e) show SEM images of various slag particle samples prepared under different acid calcination conditions. [Figure 10] As described in Example 1(h), (a) shows the XRD diffractograms of calcium titanate before and after the acid calcination process, (b) is a diagram of the 3D structure of calcium titanate, and (c)-(m) are SEM images and EDS elemental mapping for various elements of calcium titanate before and after the acid calcination process. [Figure 11] FIG. 2 is a graph of the particle size distribution of ground blast furnace (BF) slag as described in Example 2(a). [Figure 12]FIG. 1 shows the characterization results of ground BF slag as described in Example 2(a), with (a) and (b) graphs of ICP-OES and inductively coupled plasma mass spectrometry (ICP-MS) results showing elemental composition, (c) powder X-ray diffractogram, and (d) SEM image and EDS elemental mapping of BF slag particles. [Figure 13] FIG. 1 shows graphs of rate test results of rare earth elements and base metals under (a) calcination temperature condition at -1 level (200° C.) and (b) calcination temperature condition at 1 level (400° C.) with other operating parameters at intermediate levels, as described in Example 2(d). [Figure 14] 1 is a graph of the factor effect coefficients of the empirical extraction model as described in Example 2(e), showing (a) Sc results, (b) Nd results, (c) Ca results, (d) Al results, (e) Mg results, and (f) Fe results. The inset graph shows the correlation between the results predicted from the empirical model and the experimental results. [Figure 15] 1 is a graph of predicted and actual extraction efficiencies of Sc, Nd, Al, Mg, and Fe as described in Example 2(f). [Figure 16] 1 is a graph of the factor effect coefficients of the empirical extraction model as described in Example 4(e), showing (a) Fe results, (b) Nb results, (c) Cr results, (d) Mn results, and (e) Ti results. The inset graph shows the correlation between the results predicted from the empirical model and the experimental results. [Figure 17] FIG. 1 shows the results of electron probe microanalyzer (EPMA) phase mapping of the metallic phase obtained after carbothermal reduction, as described in Example 4(e). [Figure 18] FIG. 1 shows the characterization results of Fe-depleted slag as described in Example 4(g), with (a) a graph of ICP-OES results showing elemental composition, (b) a powder X-ray diffractogram, (c) EPMA phase mapping results, and (d) a secondary electron image (scale bar represents 10 μm) and EDS elemental mapping of Fe-depleted slag particles. [Figure 19]1 is a graph of the factor effect coefficients of the empirical extraction model as described in Example 4(h), showing (a) Ti results, (b) Fe results, (c) Ca results, (d) Mn results, (e) Mg results, (f) Al results, (g) Cr results, and (h) Sr results. The inset graph shows the correlation between the results predicted from the empirical model and the experimental results. [Figure 20] FIG. 2 shows two-dimensional contour plots illustrating the interaction effect of two main factors of the acid calcination water leaching process on the average extraction efficiency as described in Example 4(h), with (a) the results for calcination temperature (X1) and acid to slag mass ratio (X2), (b) the results for calcination temperature (X1) and calcination time (X3), (c) the results for calcination temperature (X1) and water to slag ratio (X4), (d) the results for acid to slag mass ratio (X2) and calcination time (X3), (e) the results for acid to slag mass ratio (X2) and water to slag ratio (X4), and (f) the results for calcination time (X3) and water to slag ratio (X4). [Figure 21] FIG. 1 is a graph of predicted and actual extraction efficiencies of Ti, Fe, Ca, Mn, Mg, Al, Cr, and Sr as described in Example 4(i). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0077] Detailed Description The following detailed description and examples are illustrative and should not be construed as further limiting the scope of the present invention. On the contrary, they are intended to cover all alternatives, modifications, and equivalents that may be included as defined in this description. The objects, advantages, and other features of the method will become more apparent and be better understood upon reading the following non-limiting description and by reference to the accompanying drawings.

[0078] All technical and scientific terms and expressions used herein have the same definitions as those commonly understood by those skilled in the art when referring to the present technology. However, the definitions of some terms and expressions used herein are provided below for clarity.

[0079] The term "about" as used herein means approximately, in the region of, or around. When the term "about" is used in connection with a numerical value, it modifies the numerical value, for example, with a variance of 10% above or below its nominal value. This term may also take into account the probability of random error in experimental measurement, for example, due to rounding of numbers or instrumental limitations. When a range of values ​​is mentioned in this application, the lower and upper limits of the range are always included in the definition, unless otherwise indicated. When a range of values ​​is mentioned in this application, it is therefore intended to include all intermediate ranges and subranges as well as the individual values ​​included in the range.

[0080] The expression "particle size" is used herein to refer to the distribution of particle sizes d x where the value dx is the value of x% of the particles being x For example, d 10 The value is the particle size below which 10% of all particles are smaller. d 90 The value is the particle size below which 90% of all particles are smaller. Therefore, d 50 The value is the median particle size, ie, 50% of all particles are larger and 50% are smaller than that particle size.

[0081] As the term "equilibrium" is used herein, it refers to a steady state in which ongoing processes strive to change the variables, but the stated variables have no observable effect (or net effect) on the properties of the system.

[0082] As used herein, the term "pore" refers to the spaces found within a particle, i.e., the void spaces within a porous particle (intraparticle pores).

[0083] As used herein, the term "drying" refers to a process by which at least a portion of the water is removed from the material being dried. As used herein, the term "dried" or its synonym "dry" material defines a total moisture content of said material that is 5.0 wt.% or less, based on the total weight of the dried material, unless otherwise specified.

[0084] As used herein, the term "digestion" or its synonym "digesting" refers to the decomposition or dissolution of a sample in a strong acid, such as concentrated sulfuric acid (H2SO4), hydrochloric acid (HCl), and nitric acid (HNO3), to obtain a paste-like sample and then to obtain a powdered sample by increasing the temperature.

[0085] It is worth mentioning that throughout the following description, when the article "a" is used to introduce an element, it does not have the meaning of "only one", but rather means "one or more". When the specification states that a step, component, feature, or characteristic "may" be included, "might" be included, "can" be included, or "could" be included, it should be understood that the particular component, feature, or characteristic need not be included in all alternatives. When the term "comprising" or its synonyms "including" or "having" are used herein, it does not exclude other elements. For the purposes of the present invention, the expression "consisting of" is considered a preferred embodiment of the term "comprising". When a group is defined below to include at least a certain number of embodiments, it should also be understood to disclose a group preferably consisting of only these embodiments.

[0086] Various methods described herein relate to the recovery of at least one valuable element from ferrous slags (e.g., iron and steel slags) by a high-temperature hydrometallurgical process, which includes both acid calcination and water leaching, hereinafter referred to as acid calcination water leaching (ABWL).

[0087] More specifically, the present technology relates to a method for recovering at least one valuable element from iron or steel slag. The valuable element is a target metal. For example, the target metal may be selected from transition metals, platinum group metals, metalloids, post-transition metals, alkaline earth metals, and / or rare earth metals. Non-limiting examples of target metals include titanium, niobium, manganese, chromium, iron, scandium, neodymium, yttrium, lanthanum, cerium, samarium, gadolinium, dysprosium, praseodymium, europium, terbium, erbium, calcium, magnesium, aluminum, copper, silicon, ruthenium, rhodium, palladium, osmium, iridium, and platinum. Preferably, the target metal includes at least one of titanium, niobium, manganese, chromium, iron, scandium, neodymium, yttrium, lanthanum, cerium, samarium, gadolinium, dysprosium, praseodymium, europium, terbium, erbium, calcium, magnesium, aluminum, copper, and silicon. According to an important variation, the target metal includes at least one of titanium, niobium, scandium, and neodymium.

[0088] In some embodiments, two or more valuable elements may be co-recovered (or co-extracted), or one valuable element may be selectively recovered (or extracted) while preventing the co-recovery (or co-extraction) of other elements.

[0089] The iron or steel slag may include at least one component selected from the group consisting of silicon dioxide (SiO2), calcium oxide (CaO), iron (III) oxide (Fe2O3), iron (II) oxide (FeO), aluminum oxide (Al2O3), magnesium oxide (MgO), manganese (II) oxide (MnO), phosphorus pentoxide (PO5), sulfur, and combinations of at least two thereof. For example, the iron or steel slag may include primarily SiO2, CaO, Fe2O3, FeO, Al2O3, MgO, MnO, PO5, and / or sulfur.

[0090] In some cases, the steel slag is a steel furnace slag. For example, the steel furnace slag can be a basic oxygen furnace (BOF) slag, an electric arc furnace (EAF) slag, or a ladle slag. In one important variation, the steel furnace slag is an EAF slag or a BOF slag. For example, the components of the EAF slag can include, but are not limited to, FeO, Fe2O3, MnO, CaO, and combinations of at least two thereof. For example, the EAF slag is primarily composed of FeO, Fe2O3, MnO, and / or CaO.

[0091] In other cases, the iron slag is blast furnace (BF) slag. The components of BF slag may include Al2O3, MgO, and sulfur. For example, BF slag is composed primarily of Al2O3, MgO, and / or sulfur.

[0092] In some embodiments, the iron or steel slag further comprises at least one other constituent, including, but not limited to, magnesium, calcium, vanadium, tungsten, copper, lead, zinc, REEs, uranium, thorium.

[0093] For a more detailed understanding of the disclosure, reference is first made to FIG. 1, which provides a flow diagram of a method for recovering at least one valuable element from iron or steel slag, according to a possible embodiment.

[0094] As shown in FIG. 1, a method for recovering at least one valuable element (or target metal) from slag includes mixing iron or steel slag particles and an acid together to form a mixture.

[0095] The iron or steel slag particles and the acid are mixed together at an acid to iron or steel slag particle mass ratio in the range of about 0.5 to about 5. For example, the acid to iron or steel slag particle mass ratio can be in the range of about 1 to about 4, or about 1 to about 3.5, or about 1 to about 3, or about 2 to about 3, or about 1 to about 2, or about 1 to about 1.75. According to an important variation, the acid to iron or steel slag particle mass ratio is in the range of about 2 to about 3.

[0096] For example, the acid, where applicable, may be selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and mixtures of at least two thereof. In one important variation, the acid comprises sulfuric acid.

[0097] The acid can be a concentrated acid, for example, the acid can have a concentration ranging from about 95% to about 99.999%.

[0098] Still referring to FIG. 1, the method also includes calcining the mixture to digest the mixture to remove excess water and acid and produce a dry mixture comprising pyrolysis gases and at least one soluble metal salt.

[0099] The calcination is carried out at a temperature in the range of about 100° C. to about 600° C. For example, the calcination may be carried out at a temperature in the range of about 200° C. to about 600° C., or about 200° C. to about 550° C., or about 200° C. to about 500° C., or about 200° C. to about 450° C., or about 200° C. to about 400° C., or about 200° C. to about 300° C., or about 300° C. to about 400° C. According to an important variant, the calcination is carried out at a temperature in the range of about 200° C. to about 400° C.

[0100] In some embodiments, the baking is carried out for a period of at least 30 minutes. For example, the baking may be carried out for a period ranging from about 30 minutes to about 240 minutes, or from about 30 minutes to about 180 minutes, or from about 30 minutes to about 120 minutes, or from about 30 minutes to about 90 minutes, or from about 30 minutes to about 60 minutes. In one important variation, the baking is carried out for a period of about 120 minutes.

[0101] In examples where the acid comprises sulfuric acid, the soluble metal salt comprises at least one soluble metal sulfate.

[0102] In examples where the acid comprises sulfuric acid, the pyrolysis gas may comprise at least one of sulfur trioxide and sulfur dioxide. As shown in Figure 1, the pyrolysis gas produced during the calcination step may be recycled. For example, the pyrolysis gas may be reused in the mixing step, thereby reducing chemical costs and increasing the environmental sustainability of the process.

[0103] The mixing and baking steps can be performed sequentially, simultaneously, or with a partial time overlap with each other, hi some embodiments, the mixing and baking steps are performed sequentially, with the mixing step occurring before the baking step.

[0104] In some embodiments, the mixing and calcining steps are carried out in a high temperature processing equipment, such as a rotary kiln.

[0105] In some embodiments, the iron or steel slag is a by-product of an iron or steel making process (not shown in FIG. 1 ). For example, the iron or steel making process provides thermal energy to the iron or steel slag, and the iron or steel slag particles may be at an elevated temperature prior to the mixing and calcination steps, thereby reducing the energy input required to obtain the temperature required for the calcination step.

[0106] Still referring to FIG. 1, the method also includes leaching the dry mixture by adding water to produce an aqueous solution containing an aqueous leachate rich in the aforementioned target metal and a solid residue.

[0107] Water is added to obtain a water to dry mix density in the range of about 50 g / L to about 250 g / L. In at least one embodiment, the water to dry mix density ranges from about 60 g / L to about 200 g / L, or from about 75 g / L to about 200 g / L, or from about 100 g / L to about 200 g / L, or from about 125 g / L to about 200 g / L, or from about 150 g / L to about 200 g / L, or from about 55 g / L to about 200 g / L.

[0108] In some embodiments, the leaching step is carried out at ambient temperature. In some embodiments, the leaching step is carried out until the system reaches equilibrium. For example, the leaching step is carried out for a period of time ranging from about 30 minutes to about 360 minutes, or from about 120 minutes to about 360 minutes, or from about 180 minutes to about 360 minutes.

[0109] Still referring to FIG. 1, the method also includes separating the aqueous leachate enriched in said target metal from the solid residue.

[0110] In some embodiments, the separation includes filtering the aqueous solution containing said target metal-enriched aqueous leachate and a solid residue. For example, the filtering can be at least one of vacuum filtering, pressure filtering, and the like. Alternatively, in an important variation, the separation includes a settling step, in which the solid residue settles to the bottom of a vessel containing said target metal-enriched aqueous leachate to form a sediment or slurry. For example, the settling can be gravitational or centrifugal settling.

[0111] As shown in FIG. 1, the method may further include grinding the iron or steel slag to obtain iron or steel slag particles prior to mixing. According to an important variant, the grinding is performed by ball milling. For example, ball milling may activate the particles, thereby increasing the extraction efficiency. In some embodiments, the method further includes classifying and separating the iron or steel slag particles into fractions by size. For example, the slag particles may be screened and classified into narrow width fractions to obtain iron or steel slag particles having a size of less than about 200 mesh. In some embodiments, the iron or steel slag particles are substantially uniform in size. For example, the iron or steel slag particles may have a diameter in the range of about 1 μm to about 150 μm, or about 1 μm to about 140 μm, or about 1 μm to about 130 μm, or about 1 μm to about 120 μm, or about 1 μm to about 110 μm, or about 1 μm to about 100 μm, or about 1 μm to about 90 μm, or about 5 μm to about 90 μm. According to an important variant, the iron or steel slag particles have a diameter in the range of about 1 μm to about 130 μm.

[0112] Still referring to FIG. 1, according to some embodiments, the method may further include drying the iron or steel slag particles prior to mixing. For example, the drying may be performed at a temperature of at least about 50° C. For example, the drying may be performed at a temperature ranging from about 50° C. to about 80° C. For example, the drying may be performed for a period of at least about 12 hours. For example, the drying may be performed for a period ranging from about 12 hours to about 24 hours.

[0113] In some embodiments, the method further comprises stirring the aqueous solution comprising the target metal-rich aqueous leachate and solid residue (not shown in FIG. 1). The stirring and leaching may be performed sequentially, simultaneously, or with a partial time overlap with each other. In some embodiments, the stirring and leaching are performed simultaneously. For example, the stirring may be performed at a stirring speed ranging from about 150 rpm to about 650 rpm. For example, the stirring speed may be in the range of about 200 rpm to about 600 rpm.

[0114] As shown in Figure 1, the excess acid may be recovered after the separation step. For example, the recovered acid may be reused in the mixing step, thereby reducing costs and increasing the environmental sustainability of the process.

[0115] In some embodiments, the method may further include purifying said target metal-enriched aqueous leachate (not shown in FIG. 1). For example, the purification step may be performed by at least one of selective precipitation, solvent extraction, and ion exchange.

[0116] In at least one embodiment, the target metal is niobium. The acid to iron or steel slag particle mass ratio is in the range of about 2.5 to about 3.5, preferably about 3. Calcination is carried out at a temperature of about 375°C to about 425°C, preferably about 400°C. The density of the dry mixture is in the range of about 175g / L to about 225g / L, preferably about 200g / L. For example, calcination may be carried out for a period in the range of about 30 minutes to about 240 minutes, or about 30 minutes to about 150 minutes, or about 30 minutes to about 120 minutes, preferably about 120 minutes. For example, the method may include stirring the aqueous solution containing the niobium-rich aqueous leachate and the solid residue at a stirring speed in the range of about 150 rpm to 600 rpm, preferably about 150 rpm.

[0117] In some embodiments, the efficiency of extraction of niobium may be at least about 90%. For example, the efficiency of extraction of niobium may be at least about 92%, or at least about 95%, or in the range of about 92% to about 99%, or about 92% to about 98%, or about 92% to about 97%.

[0118] In at least one embodiment, the target metal is titanium. The acid to iron or steel slag particle mass ratio is in the range of about 2 to about 3. The calcination is performed at a temperature of about 200° C. to about 400° C. The density of the dry mixture is in the range of about 50 g / L to about 200 g / L, or about 60 g / L to about 200 g / L. For example, the calcination may be performed for a period of about 30 minutes to about 120 minutes, or about 30 minutes to about 90 minutes. For example, the method further includes stirring the aqueous solution comprising the titanium-rich aqueous leachate and the solid residue at a stirring speed in the range of about 150 rpm to about 550 rpm, or about 200 rpm to about 550 rpm. In one embodiment, the steel slag is electric arc furnace slag, the acid to steel slag particle mass ratio is about 3, the calcination is performed at a temperature of about 400° C., and the density of the dry mixture is about 200 g / L. Calcination is carried out for a period of about 120 minutes and the stirring speed is about 150 rpm. In one embodiment, the iron slag is BF slag, the acid to iron slag particle mass ratio is about 2, calcination is carried out at a temperature of about 200° C., and the density of the dry mixture is about 62 g / L. Calcination is carried out for a period of about 90 minutes and the stirring speed is about 600 rpm.

[0119] In some embodiments, the extraction efficiency of titanium may be at least about 90%. For example, the extraction efficiency of titanium may be at least about 92%, or at least about 95%, or at least about 97%.

[0120] In at least one embodiment, the target metal is scandium. The acid to iron or steel slag particle mass ratio is in the range of about 1.5 to about 2.5, preferably about 2. Calcination is carried out at a temperature of about 175° C. to about 225° C., preferably about 200° C. The density of the dry mixture is in the range of about 50 g / L to about 70 g / L, preferably about 60 g / L. Calcination is carried out for a period of time in the range of about 60 minutes to about 120 minutes, preferably about 90 minutes. The method may further include stirring the aqueous solution comprising the scandium-rich aqueous leachate and the solid residue at a stirring speed in the range of about 550 rpm to about 650 rpm, preferably about 600 rpm.

[0121] In some embodiments, the extraction efficiency of scandium may be at least about 70%. For example, the extraction efficiency of scandium may range from about 70% to about 98%, or from about 70% to about 89%, or from about 70% to about 85%, or from about 75% to about 85%, or from about 75% to about 82%.

[0122] In at least one embodiment, the target metal is neodymium. The acid to iron or steel slag particle mass ratio is in the range of about 1.5 to about 2.5, preferably about 2. Calcination is carried out at a temperature of about 175°C to about 225°C, preferably about 200°C. The density of the dry mixture is in the range of about 50 g / L to about 70 g / L, preferably about 60 g / L. Calcination is carried out for a period of time in the range of about 30 minutes to about 60 minutes, preferably about 30 minutes. The method may further include stirring the aqueous solution comprising the neodymium-rich aqueous leachate and the solid residue at a stirring speed in the range of about 550 rpm to about 650 rpm, preferably about 600 rpm. In some embodiments, the extraction efficiency of neodymium is less than about 60%, or less than about 40%.

[0123] In some embodiments, the extraction efficiency of iron may be at least about 85%. For example, the Fe extraction efficiency may be at least about 90%, or at least about 91%. In some embodiments, the extraction efficiency of manganese may be at least about 90%. For example, the Mn extraction efficiency may be at least about 95%, or at least about 97%. In some embodiments, the extraction efficiency of magnesium may be at least about 95%. For example, the Mg extraction efficiency may be at least about 97%, or at least about 98%. In some embodiments, the extraction efficiency of aluminum may be at least about 58%. For example, the Al extraction efficiency may be at least about 65%, or at least about 75%, or at least about 80%. In some embodiments, the extraction efficiency of chromium may be at least about 90%. For example, the Cr extraction efficiency may be at least about 95%, or at least about 97%, or at least about 98%.

[0124] For a more detailed understanding of the disclosure, reference is now made to Figure 2, which provides a schematic diagram of an ABWL recovery system 10, according to a possible embodiment. The ABWL recovery system 10 includes a high temperature treatment apparatus 12 and a water leaching unit 14. According to one embodiment, the recovery system 10 may further include a settling vessel 16.

[0125] In some embodiments, the pyroprocessing apparatus 12 is configured to receive a first feed stream 18 comprising iron or steel slag, for example, directly from an industrial discharge line (not shown in FIG. 2), and a second feed stream 20 comprising an acid, for example, sulfuric acid. As shown in FIG. 2, the pyroprocessing apparatus 12 is further configured to discharge a dry mixture 22. Still referring to FIG. 2, the water leaching unit 14 is configured to receive the dry mixture 22, and a third feed stream 24 comprising water. According to one embodiment, the water leaching unit 14 may further include an agitation device 26. The water leaching unit 14 is further configured to discharge an aqueous solution 28 comprising an aqueous leachate rich in the target metal and a solid residue. As shown in FIG. 2, the settling vessel 16 is configured to receive the aqueous solution 28 comprising the aqueous leachate rich in the target metal and a solid residue, and to discharge a solid residue 30 and a leachate rich in the target metal 32.

[0126] The present application also described various methods for the recovery of at least one valuable element from iron or steel slag by a carbothermal reduction process. For example, the carbothermal reduction process may be used alone or in combination with a high-temperature hydrometallurgical process.

[0127] In some embodiments, the carbothermal reduction process may be used in combination with a high temperature hydrometallurgical process, for example, an ABWL process as described herein.

[0128] In some embodiments, a carbothermal reduction process may occur before the high temperature hydrometallurgical process.

[0129] More specifically, the present technology also relates to a method for recovering at least one valuable element from iron or steel slag. The valuable element is a target metal. For example, the target metal may be selected from transition metals, metalloids, post-transition metals, alkaline earth metals, and / or rare earth metals. Non-limiting examples of target metals include iron, calcium, silicon, manganese, aluminum, chromium, strontium, copper, nickel, titanium, niobium. According to an important variant, the target metal includes at least one of iron, manganese, chromium, niobium, magnesium, and aluminum. In some embodiments, the steel slag is an EAF slag. For example, the EAF slag may include at least one of iron, manganese, chromium, magnesium, niobium, and aluminum.

[0130] In some embodiments, two or more valuable elements may be co-recovered (or co-extracted), or one valuable element may be selectively recovered (or extracted) while preventing the co-recovery (or co-extraction) of other elements.

[0131] In some embodiments, at least one valuable element may be selectively extracted as a metallic phase from iron or steel slag by a carbothermal reduction process. For example, at least one of iron, manganese, chromium, and niobium may be selectively extracted as a metallic phase from iron or steel slag by a carbothermal reduction process. In one important variation, iron is selectively extracted as a metallic phase.

[0132] In some embodiments, at least one valuable element may be selectively extracted as a metallic phase from the iron or steel slag by a carbothermal reduction process, and at least one other valuable element may be extracted by a subsequent high-temperature hydrometallurgical process. For example, at least one of magnesium and aluminum may be extracted by a subsequent high-temperature hydrometallurgical process. In some examples, at least one of iron, manganese, chromium, and niobium may be selectively extracted as a metallic phase from the iron or steel slag by a carbothermal reduction process, and at least one of magnesium and aluminum may be extracted by a subsequent high-temperature hydrometallurgical process.

[0133] For example, a carbothermal reduction process may be used to substantially reduce the presence of at least one valuable element from iron or steel slag and to substantially increase the extraction of at least one desired metal by a subsequent high temperature hydrometallurgical process.

[0134] For a more detailed understanding of the disclosure, reference is now made to FIG. 3, which provides a flow diagram of a method for recovering at least one valuable element from iron or steel slag, according to a possible embodiment.

[0135] As shown in FIG. 3, a method for recovering at least one valuable element (or target metal) from iron or steel slag includes mixing iron or steel slag particles, and at least one reducing agent, and optionally at least one fluxing agent.

[0136] Non-limiting examples of suitable reducing agents include carbon sources such as metallurgical coal, charcoal, petroleum coke, pet coke, natural gas, or a combination of at least two thereof. In one important variation, the reducing agent comprises lignite.

[0137] In some embodiments, the iron or steel slag particles and the reducing agent are mixed at a carbon to slag mass ratio of at least about 0.06 grams of carbon per gram of iron or steel slag. For example, the iron or steel slag particles and the reducing agent are mixed at a carbon to slag mass ratio in the range of about 0.06 to about 0.12 grams of carbon per gram of iron or steel slag, inclusive. For example, the iron or steel slag particles and the reducing agent are mixed at a carbon to slag mass ratio of about 0.06 grams of carbon per gram of iron or steel slag, or about 0.09 grams of carbon per gram of iron or steel slag, or about 0.12 grams of carbon per gram of iron or steel slag.

[0138] Examples of suitable fluxes include, but are not limited to, silica (SiO2), alumina (Al2O3), and combinations of at least two thereof. In one important variation, the flux is silica. In another important variation, the flux is alumina. In another important variation, the flux includes both alumina and silica. For example, the flux may be selected for its ability to promote liquid phase formation or remove chemical impurities from the metal phase of the iron or steel slag.

[0139] In some embodiments, the iron or steel slag particles and flux are mixed at a flux to slag mass ratio ranging from 0 to about 0.1 grams of flux per gram of iron or steel slag. For example, the iron or steel slag particles and flux are mixed at a flux to slag mass ratio of 0 grams of flux per gram of iron or steel slag, or about 0.05 grams of flux per gram of iron or steel slag, or about 0.1 grams of flux per gram of iron or steel slag.

[0140] As shown in FIG. 3, the method may further include crushing the iron or steel slag prior to mixing to obtain iron or steel slag particles. For example, any suitable crushing method is contemplated. According to an important variant, the crushing is performed using at least one of a jaw crusher and a disk mill. In some embodiments, the method further includes classifying and separating the iron or steel slag particles into fractions by size. For example, the slag particles may be screened and classified into narrow width fractions to obtain iron or steel slag particles having a size of less than about 200 mesh (about 74 μm). In some examples, the iron or steel slag particles are substantially uniform in size.

[0141] Still referring to FIG. 3, the method may further include drying the iron or steel slag particles prior to mixing to remove moisture content. For example, the drying may be performed at a temperature of at least about 50° C. For example, the drying may be performed at a temperature in the range of about 50° C. to about 80° C. For example, the drying may be performed for a period of at least about 24 hours.

[0142] Still referring to Figure 3, the method may further include pelletizing the mixture including the iron or steel slag particles, the reducing agent, and the flux to create pellets. For example, the pelletizing step may be performed to substantially increase the contact area between the reducing agent and the iron or steel slag particles to increase the reduction rate during the subsequent smelting step.

[0143] In some embodiments, the pelletizing step can be carried out by pressing the mixture into pellets using a press. Any suitable pelletizing method is contemplated. According to an important variant, the pelletizing is carried out by pressing the mixture into pellets using an air / hydraulic press. In some examples, the pelletizing is carried out at a pressure of about 250 MPa for about 3 minutes, for example, under these conditions, the pellets have a diameter of about 28.6 mm.

[0144] Still referring to Figure 3, the method also includes smelting the mixture or pellets including iron or steel slag particles, reducing agents, and fluxes to obtain a slag phase and a target metal as a metal phase. The smelting step is performed by applying heat to the mixture or pellets to extract the target metal. Any suitable means of applying heat is contemplated. For example, the smelting step is performed using a melting or smelting furnace.

[0145] In some embodiments, the smelting step is carried out at a temperature in the range of about 1300°C to about 1800°C, with a heating rate of about 180°C per hour, a cooling rate of about 180°C per hour, and a holding time of about 1.5 hours. For example, the smelting step is carried out at a temperature in the range of about 1300°C to about 1700°C, or about 1300°C to about 1600°C, or about 1400°C to about 1800°C, or about 1400°C to about 1700°C, or about 1400°C to about 1600°C, or about 1500°C to about 1800°C, or about 1500°C to about 1700°C, or about 1500°C to about 1600°C, inclusive of the limits. In one important variation, the smelting step is carried out at a temperature in the range of about 1500°C to about 1600°C, inclusive of the limits. In some embodiments, the smelting step may be carried out under an inert atmosphere, for example, under an argon atmosphere. In one important variant, the smelting step is carried out at a temperature of about 1500° C. In another important variant, the smelting step is carried out at a temperature of about 1550° C. In yet another important variant, the smelting step is carried out at a temperature of about 1600° C. For example, increasing the smelting temperature reduces the viscosity of the iron or steel slag, thereby improving the separation of the target metal as metallic phase from the slag phase, resulting in an increase in extraction efficiency.

[0146] In some embodiments, the iron or steel slag is a by-product of an iron or steel making process (not shown in FIG. 3). For example, the iron or steel making process provides thermal energy to the iron or steel slag, and the iron or steel slag particles may be at an elevated temperature prior to the mixing and smelting steps, thereby reducing the energy input required to obtain the temperature required for the smelting step.

[0147] In some embodiments, the iron or steel slag particles and the reducing agent undergo an oxidation-reduction (redox) reaction that releases chemical energy. For example, the redox reaction produces heat as a by-product (an exothermic reaction). Alternatively, the iron or steel slag particles and the reducing agent undergo a redox reaction that does not release chemical energy. For example, if the redox reaction releases chemical energy, it may reduce the energy input required to obtain the temperature required for the smelting step.

[0148] The method also includes separating the metal phase (e.g., iron) from the slag phase, as shown in Figure 3. Any suitable means of separating the metal phase from the slag phase is contemplated. For example, the metal phase may be separated from the slag phase manually, for example, using any suitable mechanical separation method.

[0149] Still referring to FIG. 3 , the method further includes grinding the slag phase to obtain slag particles. For example, any suitable grinding method is contemplated. In some embodiments, the method further includes classifying and separating the slag particles into fractions by size. For example, the slag particles may be sorted and classified into narrow width fractions to obtain slag particles having a substantially reduced size. In some examples, the slag particles are substantially uniform in size.

[0150] Still referring to FIG. 3, the method may optionally include a step of further reducing the metal phase (e.g., iron) content in the slag phase to produce a slag depleted of the target metal, e.g., iron-depleted slag.

[0151] In some embodiments, further reducing the metal phase content in the slag phase may be performed by magnetic separation. Any magnetic separation method is contemplated. For example, magnetic separation may be performed using a Davis™ tube.

[0152] Still referring to Figure 3, the method may further include subjecting the target metal-depleted slag (e.g., iron-depleted slag) to a high temperature hydrometallurgy process to recover at least one valuable element from the target metal-depleted slag. For example, the high temperature hydrometallurgy process may be an ABWL process as described herein.

[0153] Recovery of valuable elements from iron or steel slags can address sustainability challenges associated with supplying strategic materials, protecting natural resources, and effectively revealing hidden values ​​of industrial waste. The technology described herein can significantly reduce the amount of waste to be disposed of, resulting in cost savings and environmental benefits. In addition, recycling the pyrolysis gases and waste leachate generated in the hydrometallurgical process can further reduce chemical costs. This acid calcination water leaching method can facilitate efficient recovery of target metals compared to conventional methods. Another advantage of the technology described herein is that it may be possible to use residual heat from the iron or steel making process for the acid calcination step, which also means reducing costs and benefiting the environment by advocating a more environmentally sustainable method. Thus, this method is applicable to the value addition of iron or steel slags.

[0154] Working Example The following non-limiting examples are illustrative embodiments and should not be construed as limiting the scope of the present invention. These examples will be better understood with reference to the accompanying drawings.

[0155] Example 1: Recovery of valuable elements from EAF slag by ABWL (a) Preparation and characterization of EAF slag particles The EAF slag samples were crushed and ground using a ball mill to obtain EAF slag particles. The EAF slag particles were then screened and classified into narrow fractions to obtain a substantially uniform particle size of about 200 mesh. The screened EAF slag particles were then dried in a convection oven for more than 24 hours.

[0156] The EAF slag particles were characterized by X-ray diffraction (XRD), scanning electron microscope attached energy dispersive spectroscopy (SEM-EDS), inductively coupled plasma mass spectrometry (ICP-MS), and inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0157] The particle size distribution of the ground EAF slag was measured using a particle size analyzer. As can be seen in Figure 4, the median particle size was about 16.0 μm, the mean particle size was about 25.3 μm, and the D 90 is approximately 58.4 μm.

[0158] The elemental composition of the EAF slag was characterized by ICP-OES after aqua regia digestion (Fig. 5(a) and (b)), as shown in Fig. 5. The EAF slag sample contained about 0.05 wt.% Nb, about 0.19 wt.% Ti, about 24 wt.% Fe, about 17 wt.% Ca, about 6 wt.% Mn, about 6 wt.% Mg, about 3 wt.% Al, and about 2 wt.% Cr.

[0159] As shown in Fig. 5(c), wüstite Fe 0.944 O, Hematite Fe2O3, Brown Millerite Ca2((Fe 1.63 Al 0.37 Several oxide phases were detected, including CrO, spinel magnesioferrite FeMgO, and larnite CaSi. Results showed that the sample was predominantly in oxide form, but other phases that were not identified due to the complexity of the sample peaks were likely present. Additionally, the low concentrations of Nb and Ti prevented the detection of phases containing these elements.

[0160] The surface morphology and elemental mapping were investigated using SEM-EDS, as shown in Figure 5(d). The EDS results showed that Nb and Ti were concentrated in specific regions and highly associated with each other and with Ca. For example, Ti may exist as calcium titanate and Nb may exist in the same compound through isomorphous substitution.

[0161] (b) Recovery of metals from EAF slag particles After drying, several samples were prepared by mixing 2 g of selected EAF slag particles prepared in Example 1(a) with concentrated (96 wt.%) H2SO4 and then calcining the mixture in a furnace at different temperatures between 200°C and 400°C. The acid calcined samples were then leached in water at a temperature of 25°C under magnetic stirring for 6 hours at different slag-to-water densities and stirring speeds. The leach solutions were diluted using a Hamilton™ Microlab 600™ dual dilution and dispensing apparatus system and characterized by ICP-OES. The samples were characterized by XRD and SEM-EDS before and after acid calcination.

[0162] (c) Experimental design and empirical model building A systematic study was conducted to investigate the quantitative effects of five operational factors, namely, acid calcination temperature (X1), acid to slag particle mass ratio (X2), acid calcination time (X3), leached pulp density (or slag particle to water density) (X4), stirring speed (X5), and combinations of these factors on the extraction efficiency of Nb, Ti, Fe, Ca, Mn, Mg, Al, and Cr.

[0163] For statistical considerations, test factors were coded into low (-1), medium (0), and high (+1) levels to allow direct comparison of the relative effects of each factor based on the magnitude of the factor model coefficients.

[0164] Detailed information about the factor levels is shown in Table 1. The upper and lower limits of the factor levels were selected based on preliminary experiments within the operating range where the response of the system could be substantially linear. [Table 1]

[0165] The five-factor experimental matrix was designed using fractional factorial design, a statistical technique used to evaluate the effect of each factor on a response and the interactions between factors.

number

[0166] Additional tests were performed with X2 of 1.25, 1.50, and 1.75 to explore the effect of X2, and kinetic studies were performed at X1 = 200° C. and 400° C. for 7 hours. These experiments unbalanced the design matrix and therefore were not included in the empirical model building data set.

[0167] For building empirical models

number

[0168] Target element i(y i The experimental response of ) was determined based on ICP-OES measurements of concentration and the calculated extraction efficiency as outlined in Equation 1.

number

[0169] In the formula, C i is the concentration of the analyte (target element) in the leachate, and V i is the volume of the leachate and m0 is the weight of each target element present in the raw sample used.

[0170] The effect of each studied factor and combination of these factors on the extraction efficiency was quantitatively evaluated by fitting the experimental data and constructing an empirical model for each target element given by Equation 2 (below) to estimate the extraction efficiency of the target elements.

number

[0171] A model was fitted to the experimental data by multiple linear regression analysis by least squares (mLLSR) as shown in Equation 3 (below), where:

number

number

[0172] The significance of each of the model parameters was estimated with a 95% confidence interval (CI) based on the two-tailed t-distribution shown in Equation 4 (below). 95% ) was determined. Parameter Variance

number

number

[0173] Analysis of variance (ANOVA) was performed on the simplified model to assess the accuracy of fit to the model. The coefficient of determination (R 2 ), the measured analyte extraction efficiency (y i ) and predicted value

number

number

[0174] (d) Determination of operational parameters and evaluation of their effects on the extraction efficiency of Nb, Ti, Fe, Ca, and other elements. The effects of ABWL operation parameters on the extraction efficiency of Nb, Ti, Fe, Ca, and other elements were investigated for X1, X2, X3, X4, and X5.

[0175] A summary of the operating conditions and the corresponding extraction efficiencies of Nb, Ti, Fe, Ca, Mn, Mg, Al, and Cr are provided below in Table 3. In these trials, the maximum extraction efficiency of Nb and Ti was 100%, while other elements such as Fe, Mn, and Mg were co-extracted with efficiencies of over 95%. [Table 3]

[0176] In Table 3, run numbers 17-21 are validation runs analyzed with standard stock solutions of Nb and Ti at concentrations of 100 mg / L, and standard stock solutions of Fe, Ca, Mn, Mg, Al, and Cr at concentrations of 1000 mg / L, supplied by Inorganic Ventures, Inc.

[0177] The effect of each factor (X1–X5) was determined, and the extraction efficiency of each element at different factor levels is shown in Figure 6.

[0178] As can be seen in Fig. 6(a), X1 has a significant positive effect on the extraction efficiency of Nb and Cr at 6 h leaching time. At the same leaching time, Ca extraction efficiency is negatively affected by the increase in X1.

[0179] As can be seen in Figure 6(e), X5 has a substantially negligible effect on the extraction efficiency of almost all elements except Ca, for which X5 has a small but positive effect. These results indicate that an X5 of 150 rpm is sufficient to bring the system to chemical equilibrium and extract almost all elements from the EAF slag, although a secondary effect of this parameter should be considered to accurately predict maximum extraction efficiency.

[0180] As shown in Figure 7(a) and (b), water leaching kinetics experiments were performed on samples calcined at 200 and 400 °C for up to 7 h, which indicated that the kinetics of the leaching process was slower for the sample prepared at X1 = 400 °C compared to the sample prepared at X1 = 200 °C, and when a sufficient amount of time was given to reach equilibrium, an increase in X1 had a positive effect on the leaching efficiency of all elements except Ca, which is probably because Ca precipitates as CaSO4, which has very low water solubility in sulfuric acid medium.

[0181] Among the operating factors studied, X2 showed the most significant positive impact on the extraction of most elements, which can be attributed to the fact that at higher acid to slag ratio, there are more acid molecules available to react with the slag particle sample, effectively resulting in a significant increase in the extraction efficiency.

[0182] It should be noted that for Fe and Ti, X2=2 was sufficient to reach their respective maximum extraction efficiencies. Thus, the center point results at factor level 0 (ratio 2) were similar to those at factor level +1 (ratio 3). Therefore, additional experiments ranging from factor level -1 (ratio 1) to level 0 (ratio 2) are necessary to gain further insight into the effect of these factors on the extraction efficiency of Fe and Ti. Additional tests were performed with acid-to-slag mass ratios of 1.25, 1.50, and 1.75, and the results are shown in Figure 7(c).

[0183] As shown in Figure 7(c), the extraction efficiencies of Nb and Ca have a linear relationship with X2, more specifically in the range of 1–3, while second-order interactions can also be observed between X2 and Fe, Ti, and other elements (second-order curvature).

[0184] (e) Empirical model building Empirical extraction models were constructed by mLLSR to assess the relative effects of the main experimental factors and aliased second-order interactions, as shown in Equation 2. Figure 8 shows the ordered factor effect coefficients of the empirical extraction models for each element.

[0185] As shown in Fig. 8(a), the factors with the largest positive impact on Nb extraction are X1 and X3. The reason behind this observation is that 5+ However, Ti in the CaTiO3 phase 4+ The possibility of replacing Nb 5+ The charge density of Ti 4+ This substitution results in a higher stability, since the charge density of X1 is higher than that of Fe(SO4)2. Therefore, more energy is required for the sulfation reaction of Nb. It is also known that Nb oxides start to dissolve in sulfuric acid medium only at high temperatures. Another reason for the positive effect of X1 and X3 is that the increase of X1 to 400 °C leads to the conversion of the (H3O)Fe(SO4)2 phase to the Fe2(SO4)3 phase, which releases H2SO4 and thus increases the extraction efficiency of Nb. The increase of X3 increases the residence time and therefore has a positive effect on the extraction efficiency.

[0186] In addition to X1 and X3, Nb extraction is slightly positively affected by increasing X2. Based on the Eh-pH diagram (or Pourbaix diagram, also known as potential / pH diagram), under the acidic conditions of the water leaching step, Nb2O5 is soluble, which explains the less pronounced effect of X2 on Nb extraction efficiency.

[0187] In the case of Ti, the extraction efficiency increases significantly with increasing X2, suggesting that in the digestion reaction, acid is the limiting reagent and therefore more Ti molecules are converted to soluble Ti sulfate when more acid molecules are available (Fig. 8(b)). As mentioned above, Ti can exist in the Ca-bearing phase as CaTiO3 with a cubic crystal structure. Since Ti is at the center of the unit cell and surrounded by Ca atoms, Ca must first react with H2SO4 to extract Ti during the acid calcination process. This explains the positive effect of X2 on Ti extraction efficiency. According to the Eh-pH diagram, Ti2(SO4)3 is only soluble at low pH, which further explains the positive effect of X2.

[0188] The other elements (Fe, Mn, Mg) have similar extraction behavior to Ti, although the magnitude of each factor effect is slightly different (Figure 8(c), (e), and (f)). X4 shows negligible or slightly positive impact on the extraction efficiency of all elements except Ca (Figure 8(d)). X5 has a negligible effect on the extraction efficiency of all elements except Ca, which can be expected since a positive effect of stirring speed can only be observed when membrane diffusion is the rate-limiting step. Therefore, a stirring speed of 150 rpm is sufficient to extract almost all elements from the EAF slag.

[0189] X4 has a positive effect on the extraction efficiency of almost all elements. For this reason, 200 g / L can be considered as sufficient to extract almost all elements from EAF slag.

[0190] Ca exhibits a unique extraction behavior, where X4 has a negative impact and X2 has a positive impact. At high X4, more solids are available for leaching if there is enough acid for extraction, but the solubility of CaSO4 is low in water. Therefore, more Ca precipitates from the solution at high X4, and hence a decrease in extraction efficiency can be observed. The positive impact of X2 can be attributed to the fact that the solubility of CaSO4 increases with increasing H2SO4 concentration in the pH range studied in this example.

[0191] Detailed information on the main and secondary effects of Nb, Ti, Fe, Ca, Mn, Mg, Al, and Cr on the extraction efficiency is shown in Table 4. [Table 4]

[0192] (f) Acid-calcined water-leaching process From this empirical extraction model, the optimized recovery conditions were determined to be High X1 (400°C, +1 level), High X2 (3, +1 level), High X3 (120 min, +1 level), High X4 (200 g / L, +1 level), and Low X5 (150 rpm, +1 level). Experiments under the optimal conditions were conducted to verify the applicability of the empirical model. The extraction efficiencies predicted from the empirical model along with the actual leaching efficiencies are shown in Table 5. [Table 5]

[0193] Extraction of 98.7% Nb, 93.4% Ti, and more than 97% Fe, Mn, and Mg was achieved under these conditions, as seen in Table 5. It was therefore concluded that the empirical model constructed in this study can successfully predict the optimal operating conditions and the corresponding extraction efficiency with high accuracy (absolute mean relative deviation (AARD) = 12.8%).

[0194] (g) Characterization of EAF slag before and after the acid calcination process The crystal structure and surface morphology of EAF slag before and after acid calcination under different operating conditions were investigated by XRD and SEM-EDS (Fig. 9). Figure 9(a) shows the XRD diffractograms of EAF slag particles before and after the acid calcination and water leaching process. The SEM-EDS images are shown in Fig. 9(b)-(e), showing raw EAF slag particles in (b), the sample prepared at 200 °C in (c), the sample calcined at 400 °C in (d), and the residue obtained after the water leaching step in (e).

[0195] These samples were selected to study the effects of acid calcination, calcination temperature, and water leaching. The XRD and SEM results are shown in Figure 9. In the EAF slags, Nb and Ti are present in trace amounts and are associated with Ca, as previously described with respect to Figure 5(d). Therefore, investigation into the digestion mechanism of Nb and Ti requires observation of the mineralogical and morphological changes of the major element (i.e., Ca or Fe) phases during digestion in the acid calcination process.

[0196] To study the mineralogical changes of Ca and Fe phases during acid calcination, samples calcined at 200 °C and 400 °C were characterized by XRD. As seen in Figure 9(a), the XRD results indicate that during the acid calcination process, Fe-dominant phases, i.e., wustite (FeO) and hematite (Fe2O3), as well as Ca-bearing phases (Ca2SiO4), are digested and replaced with sulfate phases. At lower calcination temperatures (200 °C), oxonium iron double sulfate ((H3O)Fe(SO4)2), zomolnokite (FeSO4·H2O), and anhydrite (CaSO4) are formed, whereas the iron phase is converted to anhydrous Fe2(SO4)3 at higher calcination temperatures. Based on the XRD results, at 200 °C, the following reactions are expected to occur: 4FeO (s) +8H2SO 4(aq) +O 2(g) →4(H3O)Fe(SO4) 2(s) +2H2O (g) [Formula 10] CaSiO 4(s) +2H2SO 4(aq) →2CaSO 4(s) +H4SiO4(aq) [Formula 11]

[0197] At higher calcination temperatures (400 °C), the FeSO4·H2O and (H3O)Fe(SO4)2 phases were transformed to Fe2(SO4)3 according to the following reaction, as seen in Figure 9(a): 2(H3O)Fe(SO4) 2(s) →Fe2(SO4) 3(s) +H2SO 4(g) +2H2O (g) [Formula 12] 4FeSO4·H2O (s) +4H2SO 4(aq) →2Fe2(SO4) 3(s) +2SO 2(g) +8H2O (g) [Formula 13] 4FeSO4·H2O (s) +2H2SO 4(aq) +O 2(g) →2Fe2(SO4) 3(s) +6H2O (g) [Formula 14]

[0198] As seen in Eq. 12, the conversion of (H3O)Fe(SO4)2 to Fe2(SO4)3 releases additional H2SO4. This additional acid may participate in the sulfation reaction, thereby increasing the extraction efficiency of the target elements. Unlike FeSO4·H2O and (H3O)Fe(SO4)2, which have weak layered hydrogen bond structures, Fe2(SO4)3 produced at 400°C has a cubic crystal structure, and therefore the leaching kinetics of the sample calcined at 400°C is slower than that of the sample calcined at 200°C, as shown in Figures 7(a) and (b).

[0199] As can be seen in Figure 9(a), the residue after the water leaching step mainly consists of CaSO4, which is poorly water soluble, so the extraction efficiency of Ca is low.

[0200] The microfluidic transport environment of silicate-rich phases can sometimes result in polymerization of silica gel, which has a detrimental effect on the leaching process. As shown in Figure 9(a), the main silicate phase (CaSiO4) in the EAF slag was completely digested during the acid calcination process, and no Si-bearing phase was detected in the acid-calcined samples at both calcination temperatures. As a result, no formation of silica gel was detected during the water leaching step.

[0201] The morphology changes of EAF slag before calcination and after calcination at 200°C and 400°C, as well as after water leaching, were characterized using SEM. The raw EAF slag, shown in Figure 9(b), has a rough surface with an average grain size of 25.3 μm (Figure 4). When the slag sample was acid calcined at low temperature (200°C), the morphology changed to large plate-like crystals, consistent with the hexahedral plate-like morphology reported for (H3O)Fe(SO4)2 crystals, as shown in Figure 9(c). In contrast, the slag sample calcined at high temperature (400°C) had a cubic crystal structure, consistent with the structure of rhombohedral Fe2(SO4)3, as shown in Figure 9(d). Figure 9(e) shows the SEM image of the sample after water leaching, which is 100% CaSO4. These microstructural observations are consistent with the XRD spectrum.

[0202] (h) Mechanistic study of EAF slag extraction ABWL experiments were carried out to extract Ti from CaTiO3 as a reference sample.

[0203] Figure 10(a)-(m) show the XRD and SEM-EDS results of CaTiO3 samples before and after the acid calcination process. As shown in the XRD diffractogram in Figure 10(a), the CaTiO3 phase is mainly transformed into four different phases after the acid calcination process, namely, anhydrite (CaSO4), titanium sulfate (Ti2(SO4)3), titanium oxo sulfate (TiOSO4), and titanium oxide (TiO2). The changes in the crystal structure may suggest that the following reactions occurred during the ABWL process: CaTiO3+H2SO4→CaSO4+TiO2+H2O [Formula 15] TiO2+H2SO4→TiOSO4+H2O [Eq. 16] 4TiOSO4+2H2SO4→2Ti2(SO4)3+2H2O+O2 [Formula 17]

[0204] It has been demonstrated that when CaTiO3 reacts with H2SO4, the precipitation of anhydrite and the formation of TiO2 occur first, followed by a reaction between TiO2 and H2SO4 to form either Ti2(SO4)3 or TiOSO4.

[0205] As shown in Fig. 10(b), CaTiO3 has a cubic crystal structure with space group Pm-3m, and Ti is at the center of the unit cell and surrounded by eight Ca atoms. Therefore, to extract Ti using the acid calcination process, Ca must first be sulfated by H2SO4 to form CaSO4 (Fig. 8(b)).

[0206] Figure 10(c)-(m) show the SEM micrographs and EDS elemental mapping of the samples before and after acid calcination, and the results are in good agreement with the results of Ca and Ti obtained by XRD. In the samples before acid calcination, Ca and Ti were highly associated with each other as CaTiO3, with particle sizes less than about 3 μm and substantially smooth surfaces. However, after the acid calcination process, the particle sizes increased to about 20-30 μm, and the surfaces of the particles became significantly rough and porous. Furthermore, the elemental mapping results showed that Ti and Ca were separated and concentrated in different regions after the acid calcination process. This implies that Ca was converted to CaSO4, which easily precipitates, while Ti2(SO4)3 and TiOSO4 particles were generated after the reaction between Ti and H2SO4, which aggregated and made larger particles. It is well known that TiOSO4 has high water solubility, but a dilute sulfuric acid solution is needed to dissolve Ti2(SO4)3. TiOSO4 is likely formed at low calcination temperatures and converted to Ti2(SO4)3 at 400 °C, but the sufficiently low pH of the leachate allows both Ti phases to be readily dissolved during the water leaching process.

[0207] Example 2: Recovery of valuable elements from BF slag by ABWL (a) Preparation and characterization of BF particles The BF slag samples were crushed and ground using a ball mill to obtain BF slag particles, which were then screened and classified into narrow fractions to obtain a substantially uniform particle size of about 200 mesh.

[0208] The particle size distribution of the ground BF slag was calculated using a particle size analyzer, and the results are shown in Figure 11. As seen in Figure 11, the median particle size is about 44.75 μm, the average particle size is about 51.23 μm, and D 10 is about 11.44 μm, and D 90 is approximately 98.76 μm.

[0209] BF slag particles were characterized to identify valuable species in BF slag, obtain baseline concentrations and calculate extraction efficiencies, and elucidate reaction mechanisms with emphasis on structural, physical, and morphological changes.

[0210] The elemental composition of BF slag was characterized by ICP-OES and ICP-MS after aqua regia digestion (Figure 12(a) and (b)). ICP-OES was used for the quantification of base metals, while ICP-MS was utilized for the analysis of REEs because the effect of matrix complexity during ICP-OES measurement hinders the accurate and precise quantification of REEs in BF slag leachate.

[0211] As shown in Figures 12(a) and (b), the main components of the BF slag particles are Ca (~21.7 wt.%), Al (~10.3 wt.%), Mg (~9.4 wt.%), and Fe (~1.3 wt.%). Although it is well known that silica is the main constituent of BF slag, it was not measured by ICP-OES because the aqua regia digestion could not completely dissolve the silica. However, based on the X-ray fluorescence (XRF) results shown in Figure 12(c), the silica content was determined to be ~14.3 wt.%. The ICP-MS (Figure 12(b)) results showed that the sample contained Sc, Y, La, Ce, Pr, Nd, Sm, Gd, and Dy, with a total REE concentration of ~355 mg / kg.

[0212] XRD analysis was carried out to study the crystal structure of the BF slag particles, and the results are shown in Fig. 12(c). As shown in Fig. 12(c), the BF slag particles consist of three main oxide phases: Ca2(Mg 0.75 Al 0.25 )(Si 1.75 Al 0.25 O7) (akermanite), CaMgSiO4 (monticellite), and (Ca,Ce) (Ti,Fe 3+ ,Cr,Mg) 21 O 38 (loveringite). These results are in good agreement with the ICP-OES results.

[0213] SEM-EDS analysis was carried out to investigate the physical and morphological properties of the BF slag particles (FIG. 12(d)). The SEM results show that the BF slag particles have a rough and porous surface.

[0214] The elemental mapping results showed that Ca, Si, and Al are highly associated with each other, while Mg appears to be less associated with these elements. Fe is distributed almost uniformly on the surface of the particle in low concentrations, while Mg and Ti are concentrated in certain regions. REEs were not detected by XRD and EDS elemental mapping due to their low concentrations.

[0215] (b) Recovery of metals from BF slag particles This example illustrates the recovery of metals from BF slag particles. The screened BF slag particles from Example 2(a) were dried in a convection oven for over 24 hours.

[0216] After drying, the selected BF slag particles described in Example 2(a) were mixed with concentrated (96 wt.%-98 wt.%) H2SO4 and then calcined in a box furnace at temperatures between 200° C. and 400° C. The acid-calcined samples were then leached in water at a temperature of 25° C. using a magnetic stirrer for 6 hours. The leachate solutions were collected at specified time intervals and, after dilution, characterized by ICP-OES and ICP-MS.

[0217] The BF slag particle samples were characterized using XRD and SEM-EDS before and after acid calcination and water leaching.

[0218] (c) Experimental design and empirical model building A systematic study was conducted to investigate the quantitative effects of six operational factors, namely, acid calcination temperature (X1), acid-to-slag particle mass ratio (X2), acid calcination time (X3), water-to-slag particle density (X4), stirring speed (X5), and water-to-slag mass ratio (X6), as well as combinations of these factors, on the extraction efficiency of REEs (Sc and Nd) and base metals (Ca, Al, Mg, and Fe).

[0219] For statistical consideration, the test factors were coded into low (-1), medium (0) and high (+1) levels to allow direct comparison of the relative effect of each factor based on the magnitude of the factor model coefficient.Detailed information on the factor levels is shown in Table 6.The upper and lower limits of the factor levels were selected based on Example 1(c) and preliminary experiments. [Table 6]

[0220] To construct an empirical extraction model, we used a constant leaching time (360 min)

number

[0221] A model of the form shown in Equation 18 was then fitted to the extraction efficiency data by mLLSR. A simplified model including only significant parameters (α=0.05) was evaluated by ANOVA to provide an adequate estimate of the variance of the runs. To better illustrate the effect of kinetics on extraction efficiency at different temperatures, kinetic tests were conducted at the low and high end of the calcination temperature range while keeping other parameters at mid-factor levels.

number

[0222] A detailed description of the statistical analysis is provided in Example 1(c).

[0223] (d) Speed ​​experiment Two rate experiments, one with X1 at -1 level at 200°C and the other at +1 level at 400°C, were performed with other factors at intermediate levels (X2 = 1.25 g / g DBFS、 X3=60 minutes, X4=10mL / g ABBFS , X5=400rpm, and X6=1g / g DBFS ) to investigate the effect of time on extraction efficiency at different firing temperatures.

[0224] As shown in Figure 13, at -1 level of X1, all elements except Nd reached equilibrium within 6 hours. Al and Mg showed fast kinetics reaching a plateau at 1 hour, while the extraction efficiency of Fe and Sc increased slightly. Nd concentration continued to increase with time, indicating that it has the slowest kinetics among the elements of interest. When X1 was changed to +1 level, maximum extraction of Sc and Al was obtained within 2 hours of leaching time. The extraction kinetics of the other elements were slower, and therefore more than 6 hours were required to reach equilibrium. In general, the extraction efficiency of base metals was higher than that of REEs, and Sc showed higher extraction compared to Nd.

[0225] At a leaching time of 6 h, an increase in X1 was found to have a negative effect on the extraction efficiency of all elements except Al. Specifically, the extraction of Sc, Nd, and Fe was significantly affected by this factor, with the change in extraction efficiency changing from 52.6%, 32.8%, and 71.1% to 35.8%, 22.8%, and 57.2%, respectively.

[0226] The results of this kinetic study showed that the leaching time significantly affected the extraction process. The leaching time in further experiments was set to 360 min to ensure that equilibrium was reached in most cases.

[0227] (e) Effects of operating parameters and empirical model building Experiments were conducted to examine the quantitative effects of six operational parameters and second-order interactions between at least two of the parameters.

[0228] A total of 19 runs were performed, including three center-point runs, and leachate samples were taken after 360 min of leach time. Figure 14 shows the quantitative effects of main factors and second-order interactions based on the ordered factor effect coefficients of the empirical model for each element. Only factors with sufficient significance (α=0.05) are shown.

[0229] As shown in Fig. 14(a), the extraction efficiency of Sc was positively affected by X2, while X 12 +X 35 (calcination temperature and acid-to-slag mass ratio, calcination time and stirring speed) as well as X1 had a negative effect. The positive effect of X2 is understandable since the amount of acid controls the phase transformation from water-insoluble oxides and silicates to water-soluble sulfates. The effect of X1 is consistent with the results of the kinetic test, which already showed the negative impact of X1 on the extraction efficiency of most elements except Al. This effect may be attributed to the decomposition of sulfuric acid at high temperatures. It was found that at temperatures elevated above 250°C, liquid sulfuric acid either changed to gas phase or decomposed into SO3, SO2, H2O, and O2 gases.

[0230] As shown in Fig. 14(b), the extraction efficiency of Nd increased with increasing concentrations of X2, X4, and the two quadratic interactions (X 24 +X 36 and X 13 +X 25 ), while X1, X3, X6, and some second-order interactions (X 26 +X 34 , X 15 +X 23 +X 46 , and X 12 +X 35 ) was negatively affected.

[0231] First, at higher levels of water ratio, the solution is undersaturated and therefore more salts can be dissolved. Longer duration and higher calcination temperature may result in more active decomposition and phase transition of sulfuric acid, thereby hindering extraction. The negative effect of X6 can be explained by the fact that adding water to the slag and acid mixture lowers the boiling point of sulfuric acid and thus hinders the reaction between acid and slag in the acid calcination step. When +1 levels of X2 and X6 are used, the final concentration of acid is reduced from 98% to 49% and the boiling point is reduced from about 337°C to about 195°C. Thus, even at -1 levels of X1, the acid evaporates before reaching the set temperature and reacting with the BF slag particles.

[0232] As shown in Figure 14(c), the extraction efficiency of Al depends only on two factors, namely, X2 and X4. As shown in Figures 14(d) and (e), the extraction efficiency of Mg and Fe depends on X2, X3, X4, and several second-order interactions (X 26 +X 34 and X 16 +X 45 ), while X1, X6, and a few quadratic terms (X 24 +X 36 and X 15 +X 23 +X 46Furthermore, unlike the other elements, the dissolution of Mg improved with increasing X6. A summary of the operating conditions and the corresponding extraction efficiencies of Sc, Nd, Ca, Al, Mg, and Fe is provided in Table 8 below. [Table 8]

[0233] (f) Verification and Optimization An empirical extraction model was constructed for each element using Eq. 18 to predict the extraction efficiency under specific conditions. As shown in FIG. 15, two validation tests were conducted to evaluate the applicability of the model. The first validation test was performed at X1=400°C, X2=2g / g DBFS , X3=30 minutes, X4=16mL / g ABBFS , X5=200rpm, and X6=2g / g DBFS The results were consistent with the model predictions, with a model accuracy of 7.7%. A second validation test was performed under mild conditions (X1 = 200°C, X2 = 0.5 g / g DBFS , X3=30 minutes, X4=4mL / g ABBFS , X5=600rpm, and X6=0g / g DBFS ) and using these conditions, the actual extraction efficiency of REE and Al was determined to be less than 11% and the model accuracy was 15.8%.

[0234] In order to maximize the economic benefits from all the studied elements, an optimization test was carried out. The conditions that satisfied this optimization were: X1 = 200°C, X2 = 2g / g DBFS ,X3=90min,X4=16mL / g ABBFS , X5=600rpm, and X6=0g / g DBFS The expected profit from all elements was 264.3 USD / ton. DBFS The actual profit is 238.1 USD / ton. DBFS (Accuracy = ±20.4%). The prices of Sc, Nd, Al, Mg, and Fe considered in the optimization calculations are shown in Table 9. [Table 9]

[0235] Optimization studies were carried out to maximize the economic benefits derived from REEs.

[0236] The conditions that satisfy this optimization are X1 = 200°C, X2 = 2g / g DBFS , X3=30 minutes, X4=16mL / g ABBFS , X5=600rpm, and X6=0g / g DBFS As can be seen in Figure 15, the actual extraction efficiency was similar to that predicted with a high degree of accuracy (±12.8%). The predicted and actual benefits considering REE were 69.0 and 71.1 USD / ton, respectively. DBFS It was calculated to be.

[0237] The overall validation and optimization results demonstrate that the empirical model can successfully predict the optimal conditions and extraction efficiency.

[0238] Example 3: Optimized parameters for recovery of individual target metals by ABWL (a) Recovery of valuable elements from EAF slag The optimized parameters for recovery of Nb, Ti, Fe, Ca, Mn, Mg, and Al from EAF slag as determined in Example 1 are shown in Table 10 below. [Table 10]

[0239] (b) Recovery of valuable elements from BF slag The optimized parameters for recovery of Sc, Nd, Ca, Al, Mg, and Fe from BF slag as determined in Example 2 are shown in Table 11 below. [Table 11]

[0240] Example 4: Recovery of valuable elements from EAF slag by carbothermal reduction followed by ABWL (a) Preparation and characterization of EAF slag particles The EAF was first crushed and ground using a jaw crusher and disk to obtain a substantially uniform particle size of about 200 mesh (about 74 μm). The ground slag samples were dried in a convection oven at a temperature of 50° C. for more than 24 hours to remove the moisture content.

[0241] The samples were then mixed with lignite and fluxes (SiO2 and / or Al2O3), and the mixture was then pelletized using an air / hydraulic press at a pressure of about 250 MPa for 3 minutes (pellet diameter = 28.6 mm). The pellets were then placed in graphite crucibles and smelted in a box furnace at different set temperatures (1500°C or 1600°C, heating rate 180°C / h, cooling rate 180°C / h, holding time 1.5 hours) under argon atmosphere. After smelting, the metallic Fe phase and the slag phase were manually separated using a Dremel™ and hammer, and the slag phase was crushed using a mixer mill. To reduce the Fe content in the slag phase, the crushed slag samples were magnetically separated using a Davis™ tube. The Fe-depleted slag samples thus obtained were then dried in a convection oven and digested in aqua regia using a microwave digestion apparatus (heat-up time 40 min, hold time 30 min, set temperature 220°C) for characterization.

[0242] The dried Fe-depleted slag samples were then mixed with concentrated sulfuric acid. The mixture was placed in a porcelain crucible and calcined in a muffle furnace. The acid-calcined samples were then water leached at ambient temperature and pressure using a magnetic stirrer. The leachate solution thus obtained was then filtered and diluted using a Hamilton™ Microlab 600™ dual dilution and dispensing device system for characterization. Certain solid samples before and after each process were also prepared for post-mortem characterization.

[0243] (b) Experimental design and empirical model building For the carbothermal reduction process, a fractional factorial design was used to design an experimental matrix and build an empirical model, resulting in process optimization. A systematic study was conducted to investigate the effects of four operating parameters, namely smelting temperature (X1), carbon-to-slag mass ratio (X2), flux-to-slag mass ratio (X3), flux type (X4), and the second-order interactions of these factors, on the composition of the slag phase. A low level of smelting temperature (X1) was selected based on the preliminary test results to ensure complete melting of the pellets and clear phase separation between metallic Fe phase and slag phase. The stoichiometric calculation results showed that at least 0.06 g of carbon per gram of EAF slag was required to reduce all the iron in the slag in the form of FeO, and therefore a low level of carbon-to-slag mass ratio (X2) of 0.06 g / g EAF slag was selected. EAFS Due to the high calcium content in the EAF slag, the flux used in this study was decided to be silica or alumina.

[0244] For the ABWL process, the effects of four operational parameters, namely calcination temperature (X1), acid-to-slag mass ratio (X2), calcination time (X3), and water-to-slag ratio (X4), on the extraction of the elements of interest (Ti, Fe, Ca, Mn, Mg, Al, Cr, and Sr) were investigated using response surface methodology.

[0245] For this process, the boundaries of the factor levels were selected within the operating range where the system response can be relatively linear, based on preliminary test results and the operating ranges of similar processes in the literature (Anawati et al., Waste Management 95 (2019): 549-559; Demol et al., Hydrometallurgy 179 (2018): 254-267; Kim et al., Hydrometallurgy 191 (2020): 105203; Meshram, et al., Journal of Cleaner Production 157 (2017): 322-332; Sadri et al., International Journal of Mineral Processing 159 (2017): 7-15; Safarzadeh et al., Mining, Metallurgy & Exploration 29, no. 2 (2012): 97-102; and Safarzadeh et al., International Journal of Mineral Processing 124 (2013): 128-131).

[0246] Based on fractional factorial design and response surface methodology, two experimental matrices were designed for the carbothermal reduction process and the ABWL process, respectively. For the carbothermal reduction process, a series of

number

number

number

number

number

number

[0247] (c) mineralogical, morphological, and compositional characterization The mineralogical properties of the solid samples were studied by XRD. Morphological and compositional analyses were performed by SEM-EDS. For compositional characterization of the solid samples, an electron beam microanalyzer was used. The elemental concentrations in the liquid samples were measured by ICP-OES. The silica content of the solid samples was quantified by XRF. The carbon content of the metallic Fe phase was analyzed using a LECO (CS 444 Carbon-Sulfur Analyzer).

[0248] (d) Characterization of EAF slag The chemical composition of the EAF slag was investigated by ICP-OES and XRF analysis after digestion with aqua regia (Table 12). As shown in Table 12, the main component of the EAF slag is Fe, which accounts for 24.3 wt.% of the composition. The high Fe content confirmed that the EAF slag sample was suitable for undergoing the carbothermal reduction process. As shown in Table 12, the EAF slag also contains Ca (17.3 wt.%), Si (7.5 wt.% as determined by XRF), Mg (5.5 wt.%), Mn (5.5 wt.%), Al (2.5 wt.%), and Cr (1.9 wt.%). The EAF also contains trace amounts of Ti (1862 mg / kg), Na (1184 mg / kg), Nb (489 mg / kg), Sr (341 mg / kg), Cu (303 mg / kg), and Ni (300 mg / kg). [Table 12]

[0249] (e) Effects of operating parameters and empirical model building Carbothermal reduction was performed to selectively separate Fe, Nb, Cr, Mn, and partially Ti by reporting them in the metal phase while other elements were reported in the slag phase. Based on fractional factorial design,

number

[0250] The ordered factor effect coefficients with full significance (α=0.05) for the concentration of each element in the slag phase are shown in Figure 16. It should be noted that the goal of this process is to minimize the concentrations of the five elements in the slag phase such that they are expected to be reported in the metal phase.

[0251] As shown in FIG. 16(a), the Fe concentration in the slag phase was negatively affected by three main factors: X1, X2, and X3. In other words, an increase in these factors resulted in a decrease in the Fe concentration in the slag phase, which is desirable. The negative effect of X1 can be understood because a higher X1 reduces the viscosity of the slag and consequently improves the separation of the metal phase from the slag phase. The inverse correlation between X1 and slag viscosity is shown in Equation 22.

number

[0252] The Fe concentration in the slag phase was observed to increase with decreasing X2. EAFS ) means that this level was selected based on the stoichiometric value of carbon to reduce all the Fe in the slag, but was not sufficient to reduce all the Fe. This phenomenon can be explained by the carbide formation of Mn and Cr that occurs during the smelting process.

[0253] The EPMA elemental mapping results of the metallic phase were obtained after the carbothermal reduction process (run 10) and the results are shown in Figure 17. The results showed a fairly strong correlation between the C, Mn, and Cr rich regions where the Fe concentration was relatively low. This indicates that the Fe-Mn-C, Fe-Cr-C, and Fe-Mn-Cr-C alloy formation reactions took place and consumed a significant amount of the carbon present in the mixture. Based on the chemical composition of the EAF slag, it was calculated that the low level of X2 (0.06 g carbon per g EAF slag) could not completely reduce the FeO phase present in the EAF slag to metallic Fe when more than 30 wt.% Mn and Cr participate in the carbide formation reaction. However, this reaction could not affect the FeO reduction rate when the X2 was at a medium level (0.09 g carbon per g EAF slag) and a high level (0.12 g carbon per g EAF slag).

[0254] The negative effect of X3 can be explained by the basicity of the slag. The four-parameter basicity (R) was calculated based on Equation 23:

number

[0255] Without the addition of fluxing agents, the slag phase obtained after the carbothermal reduction process has a substantial excess of basicity (R = 2.584) due to the high basic oxide content in the EAF slag. This substantial excess of basicity may increase the melting temperature of the EAF slag, which results in the precipitation of solids, i.e., CaO and MgO, and a high apparent viscosity of the EAF slag. Thus, the metallic iron droplets can be more easily trapped in the slag. The fluxing agents used in this process are either acidic (SiO2) or amphoteric (Al2O3). Considering the basic conditions and low alumina content (<15 wt%) in the system, Al2O3 is likely to act as an acidic oxide. Adding these acidic fluxing agents, for example, may lower the basicity and liquidus point of the EAF slag, resulting in a clear separation between the metal and slag phases. Thus, the Fe content in the slag phase is reduced in the presence of SiO2 or Al2O3. To verify these explanations, a 0.09 g / g EAFS The carbothermal reduction of EAF slag samples with and without fluxes (SiO2 or Al2O3) at carbon to slag mass ratio of 0 (level) was simulated using FactSage software, and the results confirmed that the liquidus point of the slag was significantly reduced when either SiO2 or Al2O3 was added as flux.

[0256] The concentrations of other elements in the slag phase showed similar trends compared to those of Fe. However, the type of flux (X4) showed an additional positive effect on the concentrations of Nb and Mn. The concentrations of Nb and Mn in the slag phase are lowered when SiO2 is used as the flux instead of Al2O3 (Figure 16(b) and (d)). This can be attributed to the fact that SiO2 is a stronger acidic oxide than Al2O3. The presence of SiO2 contributes to lowering the liquidus of the EAF slag and improving the phase separation, while Al2O3 has the same effect, but to a lesser extent. Furthermore, X2 was caught to have a positive effect on the concentration of Mn in the slag phase, unlike the other elements. This can be explained by the desulfurization of metals by Mn. As described in Example 4(a), lignite was used as the reducing agent, and this type of coal contains about 0.4-1.0 wt.% sulfur, making it the main sulfur source. Substantially higher sulfur contents can make the metal product brittle, less weldable, and more susceptible to corrosion, so it is desirable to keep the sulfur content below 0.015 wt.% (Schrama et al., Ironmaking & Steelmaking 44, no. 5 (2017): 333-343). MnO, along with CaO and MgO, is one of the primary desulfurization agents utilized to transfer sulfur from the metal to the slag via the following reaction (Eq. 24): FeS (metal) +Mn (metal) →Fe (metal) +MnS (slag) [Formula 24]

[0257] When more carbon (high levels of X2) is introduced into the system, more sulfur is introduced and reacts with Fe metal, resulting in the formation of more FeS. According to Le Chatelier's principle, desulfurization occurs actively through the formation of MnS, which appears in the slag phase.

[0258] Post-mortem characterization of the metallic phase obtained after carbothermal reduction was performed using XRD and EPMA analysis. The X-ray diffractogram showed that the metallic phase was composed of Fe, Fe3C, and C, confirming a clear separation between the metallic and slag phases. The presence of niobium phosphide was observed with EPMA.

[0259] (f) Optimization and validation of the carbothermal reduction process Based on the experimental results and factor effect coefficients, an empirical model was constructed to predict the concentrations of Fe, Nb, Cr, Mn, and Ti in the slag phase. The empirical model for Fe concentration is shown in Equation 25:

number

[0260] Two validation tests were conducted to evaluate the predictability of the model. As shown in Table 14, the results showed that the model had high model accuracy for predicting the concentrations of five elements (Fe, Nb, Cr, Mn, and Ti) in the slag phase (mean absolute relative deviation (AARD) of 15.6 and 12.1% for each test set). [Table 14]

[0261] The carbothermal reduction process was then optimized to minimize the Fe concentration in the slag phase. The optimized conditions included a high level of smelting temperature (X1, 1600°C) and carbon to slag mass ratio (X2, 0.12 g / g EAFS ), as well as low levels of flux to slag mass ratio (X3, 0 g / g EAFS ) and flux type (X4, silica). A minimum amount of Fe in the slag phase at a concentration of 1620 mg / kg, along with metallic iron enriched in Mn, Cr, and Nb (about 70 wt.% Fe, about 4.14 wt.% C, about 17 wt.% Mn, about 7 wt.% Cr, and about 0.2 wt.% Nb) was obtained after the smelting process under the optimized conditions (Table 14). Table 15 shows the composition of the raw EAF slag and the composition of the metallic and slag phases obtained after the carbothermal reduction process under the optimized conditions. [Table 15]

[0262] (g) Acid-water leaching results and characterization of Fe-depleted slag The slag produced after the carbothermal reduction process under the optimized conditions was thoroughly characterized using ICP-OES, XRD, EPMA, and SEM-EDS after aqua regia digestion (Figure 18). Most of Fe, Nb, Cr, Mn, and partially Ti were reported in the metallic phase, and the concentrations of these elements in the slag phase were minimal.

[0263] Figure 18(a) shows the elemental composition of the Fe-depleted slag. The slag sample was mainly composed of Ca (30.2 wt.%), Mg (11.7 wt.%), and Al (4.9 wt.%), while trace amounts of Mn (6803 mg / kg), Ti (2993 mg / kg), Fe (1620 mg / kg), Sr (628 mg / kg), and Cr (175 mg / kg) were present. Based on the XRD results shown in Figure 18(b), the slag was found to contain four phases, namely, larnite (Ca2SiO4), magnesium iron oxide (Mg2SiO4), and ferric oxide (Fe2SO4). 0.91 Fe 0.09 The slag consists of SiO, CaCO, and gehlenite. EPMA phase mapping results further confirm that the slag contains these four phases along with small amounts of chromite contributing trace amounts of Fe and Cr (Figure 18(c)). EDS elemental mapping in Figure 18(d) shows that Ca and Si are highly associated with each other, confirming the presence of CaSiO. Aluminum is also present in some cases in the Ca and Si rich regions, indicative of CaAlSiO. Mg is only consistent with oxygen, confirming the presence of Mg 0.91 Fe 0.09 The SEM images confirm the presence of O. The Ca2Al2SiO7 has a sharp morphology with a smooth surface, while the Ca2SiO4 and Mg 0.91 Fe 0.09 O indicates a layered structure (Figure 18(d)).

[0264] (h) Effects of Operating Parameters and Empirical Model Building For the ABWL process, the circumscribed center composite experimental matrix was designed using response surface methodology, and the second-order empirical extraction model of the target elements was constructed. The detailed experimental conditions and the corresponding extraction efficiencies of Ti, Fe, Ca, Mn, Mg, Al, Cr, and Sr are shown in Table 16. The ordered factor effect coefficients with sufficient significance (α=0.05) for the extraction efficiency of each element are shown in Figure 19. [Table 16] TIFF2025028919000040.tif16162

[0265] As seen in Figure 19, the acid to slag mass ratio (X2) showed a large positive effect on the extraction of all elements. This may suggest that H2SO4 is the limiting reagent for the digestion reaction. At 0 level of acid to slag ratio (1.5g / g), it was calculated that there was an equivalent amount of H2SO4 that could completely react with the slag sample in the system, and therefore, the digestion reaction did not occur sufficiently at the lower levels of acid ratio (0.5g / g and 1g / g).

[0266] Unlike other elements, Ca and Sr were also positively affected by the water-to-slag ratio (X4) (Figures 19(c) and 19(h)). This may be due to the low water solubility of CaSO4 and SrSO4. The solubility of CaSO4 and SrSO4 in water is 2.00 g / L and 0.117 g / L, respectively, which is less than 1 / 100 of the solubility of common salts. Therefore, a higher water-to-slag ratio was needed to increase the extraction of Ca and Sr.

[0267] Calcination temperature (X1) showed a negative effect on the extraction of all elements of interest. This effect can be explained, for example, by the phase transition and decomposition of H2SO4 at high calcination temperatures. At temperatures above 250°C, liquid H2SO4 begins to evaporate and decompose into SO2, SO3, H2O, and O2 gases, and therefore liquid H2SO4 cannot exist at temperatures higher than 350°C. This phenomenon results in a significant loss of liquid H2SO4, which is highly reactive with slag particles. Calcination temperature is potentially the main contributing factor to the mass loss, confirming the adverse impact of this factor. Higher levels of acid-to-slag mass ratio (X2), calcination time (X3), as well as the calcination temperature x acid-to-slag mass ratio (X4) significantly reduced the mass loss. 12 ) and baking temperature x baking time (X 13 ) was also found to accelerate the mass loss of the acid and slag mixture. This was due to the fact that X3, X 12 , and X 13 Although greater mass loss occurred at higher levels of X2, explaining why in most cases it had a negative effect on extraction, the higher absolute amount of available H2SO4 molecules causes a positive effect of this factor on extraction.

[0268] Figure 20 shows a 2D contour plot visualizing the interaction effect of the two main factors on the average extraction efficiency of all elements except Ca, which was not considered since the process was designed to recover Ca as gypsum (CaSO4·2H2O) in the residue. As can be seen, the acid to slag mass ratio (X2) plays an important role in increasing the overall extraction efficiency, while the other factors do not have a significant impact on the extraction.

[0269] (i) Optimization of the acid calcination water leaching process Based on the factor effect coefficients obtained after the experimental design test, the ABWL process was optimized for maximization of the extraction of Ti, Fe, Mn, Mg, Al, Cr, and Sr. The extraction efficiency of calcium was not considered in the process optimization because Ca was recovered as gypsum (CaSO4·2H2O) in the residue.

[0270] Response surface methodology allows for the exploration of a wider range of response surfaces as long as the Euclidean distance is kept constant. Thus, unlike fractional factorial design, the optimized factor levels are not restricted to -1 and 1, but can be any number. However, it should also be noted that while the predicted extraction efficiency can exceed 100% under certain conditions, the actual efficiency cannot exceed 100%, and therefore an extraction efficiency ≦100% was added as a constraint for the process optimization. Two optimized conditions were then determined with and without the constraint of factor levels restricted to -1 and 1. Figure 21 shows the optimization results (i.e., extraction efficiency) of the acid calcination water leaching process. The results showed that extraction efficiencies of over 80% were achieved for almost all elements except Ca and Sr, regardless of the constraint of factor levels. The low efficiency of Ca and Sr may be due to their low water solubility.

Claims

1. A method for recovering at least one target metal from iron or steel slag (hereinafter referred to as "steel slag, etc.") in an electric arc furnace or basic oxygen furnace, comprising the steps of: (a) mixing the particles, such as steel slag, with at least one reducing agent, the mass ratio of the reducing agent to the particles, such as steel slag, being in the range of about 0.06 to 0.12, and at least one flux, the mass ratio of the flux to the particles, such as steel slag, being in the range of 0 to about 0.1, to form a mixture, a., wherein the flux is selected from the group consisting of silica, alumina, and a combination of silica and alumina; (b) smelting the mixture at a temperature of about 1300° C. to about 1800° C. to form a metal phase and a slag phase comprising the first target metal; (c) separating the metal phase containing the first target metal from the slag phase to produce a metal phase containing the target metal and an iron-depleted slag. The method includes:

2. The method of claim 1 , wherein the flux is alumina or a combination of alumina and silica.

3. the reducing agent comprises a carbon source; or The particles, such as steel slag, have a size of less than 200 mesh. The method according to claim 1 or 2.

4. below: A step of crushing the particles such as steel slag before step a; classifying and separating the particles, such as steel slag, into fractions according to size; Before step a, a step of drying the particles such as steel slag; prior to step b., pelletizing the mixture; grinding the slag phase to obtain slag particles; and Reducing the iron content in the slag phase to produce an iron-depleted slag. The method of any one of claims 1 to 3, further comprising at least one step selected from the group consisting of:

5. The method according to any one of claims 1 to 4, wherein the separation in step c) is carried out by a mechanical separation method.

6. The method according to any one of claims 1 to 5, wherein the smelting in step b is carried out at a temperature of about 1500°C to about 1600°C.

7. 7. A method according to any one of claims 1 to 6, wherein the particles, such as steel slag, and the reducing agent undergo an oxidation-reduction (redox) reaction which releases chemical energy.

8. 8. The method according to any one of claims 1 to 7, wherein step a comprises mixing the at least one reducing agent in a mass ratio of the reducing agent to the particles, such as steel slag, of about 0.

05.

9. 8. The method according to any one of claims 1 to 7, wherein step a comprises mixing the at least one reducing agent in a mass ratio of the reducing agent to the particles, such as steel slag, of about 0.

1.

10. 10. The method of any one of claims 1 to 9, wherein the reducing agent comprises a carbon source selected from the group consisting of metallurgical coal, charcoal, petroleum coke, pet coke, natural gas, and combinations of at least two thereof.

11. 11. The method according to any one of claims 1 to 10, wherein the mass ratio of the reducing agent to the particles, such as steel slag, is about 0.06, about 0.09, about 0.10 or about 0.

12.

12. 12. The method according to any one of claims 1 to 11, comprising, prior to step a, a step of drying the particles such as steel slags, said drying being carried out at a temperature of at least about 50°C and said drying being carried out for a period of at least about 24 hours.

13. 13. The method of any one of claims 1 to 12, wherein step b is carried out at a temperature range of about 1300°C to about 1700°C, about 1300°C to about 1600°C, about 1400°C to about 1800°C, about 1400°C to about 1700°C, about 1400°C to about 1600°C, about 1500°C to about 1800°C, about 1500°C to about 1700°C, or about 1500°C to about 1600°C.

14. 14. The method of any one of claims 1 to 13, further comprising subjecting the iron-depleted slag to a high temperature hydrometallurgical process to recover a second target metal.

15. The step of subjecting the iron-depleted slag to a high temperature hydrometallurgical process to recover a second target metal comprises the steps of: mixing the iron-depleted slag particles with an acid in a mass ratio of the acid to the iron-depleted slag particles in a range of about 0.5 to about 5 to produce a further mixture, wherein the acid is selected from the group consisting of sulfuric acid, hydrochloric acid, and mixtures of at least two thereof; calcining the further mixture at a temperature of about 100° C. to about 600° C. to remove excess moisture and the acid and produce a dry mixture comprising pyrolysis gases and at least one soluble metal salt; leaching the dry mixture by adding water to a density in the range of about 50 g / L to about 250 g / L to produce a mixture comprising an aqueous leachate enriched in the second target metal and a solid residue; separating said second target metal-rich aqueous leachate from said solid residue; The method of claim 14, comprising:

16. 16. The method of claim 14 or 15, wherein the second target metal is selected from the group consisting of titanium, niobium, manganese, chromium, scandium, neodymium, yttrium, lanthanum, cerium, samarium, gadolinium, dysprosium, praseodymium, europium, terbium, erbium, calcium, magnesium, aluminum, copper, silicon, ruthenium, rhodium, palladium, osmium, iridium, and platinum.

Citation Information

Patent Citations

  • Method of treating waste slug from oxygen steel production

    JP1978081415A

  • Method for recovering valuable metal from converter slag

    JP1987013541A